Residual strength and failure-mode transitions of loess–steel interface under large-displacement ring shear - Jichao Zhang; Zhihua Yao; Xiaowen Lin; Binxian Shen; Xiaolei Chong; Yaohua Zhang; Huihui Zhao (European Journal of Environmental and Civil Engineering, 2026)

Enhancing herbaceous biomass combustion in an industrial-scale CFB boiler using iron-based oxygen carriers as bed material - Guang Sun; Lin Li; Chong Liu; Tianxin Li; Heng Liu; Lunbo Duan (Fuel, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Effects of bergaptol on subacute ruminal acidosis in Hu sheep rumen epithelial cells and Saanen dairy goats - Mengyan Liu; Zhe Guo; Chong Zhang; Tao Zhong; Aline Freitas-de-Melo; Caode Jiang; Tao Lin (Small Ruminant Research, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

S-methoprene affected the population growth of Ephestia elutella (Hübner) - Lin-chong An; Xiao-fei Yu; Si-qi Wan; Mao-fa Yang (Journal of Stored Products Research, 2026)

Ligand-selective AHR regulation in benzo[a]pyrene-induced colonic barrier injury: Indole-driven functional reprogramming and microbiota-dependent tryptophan defense - Xiaolei Guo; Fan Peng; Qinfeng Cai; Xuechun Lin; Anqi Yin; Fangyi Xu; Jing Zhao; Shuiqing He; Chong Tian; Chenjiang Ying (Journal of Hazardous Materials, 2026)

Spatiotemporal multiscale quantitative evaluation of formation damage during drill-in operations in deep fractured tight reservoirs based on geoscience-engineering integration - Chong Lin; Yili Kang; Lan Wang; Hai He; Gao Li; Hongling Zhou (Geomechanics for Energy and the Environment, 2026)

Molecular characterization and expression analysis of three complement genes: C4B, C6 and C7 in Mastacembelus armatus under Aeromonas veronii infection - Kaifeng Wang; Ziyan Deng; Shengyue Lin; Min Zhang; Guojun Cai; Zihang Xie; Chong Han; Qiang Li (Fish & Shellfish Immunology, 2026)

Reaction engineering of a solar chimney-driven honeycomb photocatalytic reactor for outdoor low concentration methane oxidation - Hanbing Xiong; Tingzhen Ming; Yongjia Wu; Liwen Mu; Renaud de Richter; Wenting Lin; Wenyu Li; Chong Peng; Wei Li (Chemical Engineering Journal, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

From leaf to landscape: Leaf-based machine learning for genus and species-level mangrove classification of UAV-acquired hyperspectral data - Han Shen Lim; Wai Chong Chia; Yunli Lee; Mei-Hua Lin; Ong Cieh Wong; Stacey Sing; A Aldrie Amir; Kian Meng Yap (Remote Sensing Applications: Society and Environment, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

Physical morphology of conductive carriers shapes anaerobic biofilm development and methanogenesis - Lu Zhang; Wen He; Zu-xiang Yan; Tong-yi Yang; Lin-zhi Zhai; Xiu-jie Wang; Qian-qian Jia; Ze-chong Guo (Bioresource Technology, 2026)

Developing a fusion algorithm based on UAV and mobile monitoring to quantify black carbon emissions from various types of planned straw residue burning - Jing Fu; Weiwei Chen; Chong Hui; Xue Yang; Lin Liang; Bowen Shi (Atmospheric Environment, 2026)

Sexually dimorphic expression and hormonal responsiveness of steroidogenic Cyp genes during gonadal differentiation in mandarin fish - Jieming Zhang; Shengyue Lin; Ziyan Deng; Weijian Chen; Guojun Cai; Min Zhang; Lilin Zhan; Chong Han; Jian Gong; Qiang Li (Fish Physiology and Biochemistry, 2026)

Evidence for plant resource utilisation from the Southern Dynasties period (5th–6th century ce) in South China: a study of macrobotanical remains from the administrative office of Yuezhou Ancient City, Guangxi, China - Zixian Jiang; Chong Yu; Xue Yan; Weiyan Wei; Junlei Zheng; Qiang Lin; Chuenyan Ng (Vegetation History and Archaeobotany, 2026)

PROMETHEUS clinical trial protocol: tailoring healthy ageing with lifestyle and nutraceuticals - Ajla Hodzic Kuerec; Lihuan Guan; Weilan Wang; Duarte Barros; Wejdan M. Alenezi; Jozo Grgic; Vanessa K. Wazny; Jordi Morwani-Mangnani; Mazzarine Dotou; Dingding Zhang; Tong Chen; Jiaqiu Wang; et al. (GeroScience, 2026)
The d emographic shift toward an older population is accelerating the prevalence of age-related diseases. Precision geromedicine represents a paradigm shift in targeting the biological processes of ageing to optimise health and healthspan, which likely requires multimodal tailored interventions. PROMETHEUS, as part of the XPRIZE healthspan semi-finalist competition, is an 8-week feasibility and exploratory study including 20 middle-aged-to-older participants who received a multimodal intervention comprising fundamental and augmented interventions. The fundamental interventions include sleep and dietary recommendations; supplementation with whey protein, creatine, and fucoidan; supervised exercise with an exergaming component (dual-task cognitive-physical training); motivational interviewing; and cognitive behavioural therapy. The augmented intervention is further personalised based on predefined gerotypes, reflecting individual ageing patterns beyond chronological age. At baseline, urolithin A, nicotinamide mononucleotide, and/or multivitamin-multimineral were prescribed to participants based on their muscle mass, VO 2 peak, and cognitive performance. At mid-intervention, interventions were adjusted based on individual response, including dose escalation and/or the addition of ergothioneine for inadequate improvement in cognition. Primary outcomes include measures of muscle strength and mass, immune function and cognitive performance, and feasibility indicators such as adherence and trial completion. Secondary outcomes include assessments of other biological, clinical, and digital biomarkers of ageing, as well as qualitative indicators of motivation and personal values. This study is aimed at investigating the recruitment feasibility, safety, adherence, and exploratory outcome trajectories of a multimodal, personalised precision geromedicine intervention protocol based on individual participant’s baseline characteristics and interim responses. These findings will also inform the design of a subsequent 12-month, randomised controlled trial evaluating personalised lifestyle and nutraceutical strategies with the potential to incorporate repurposed pharmacological agents to optimise age-related health outcomes.

Effect of maize seed posture on filling performance of a positive-pressure pneumatic seed-metering device with irregular seed-holes - Chong Liu; Lijing Liu; Chunlei Wang; Zhongjun Liu; Donghong Lin; Abdul Mounem Mouazen (Computers and Electronics in Agriculture, 2026)

Predictable April 2025 extreme dust storm in Southern China - Wenqi Zhang; Mei Chong; Huiwen Xiao; Shengkai Wang; Qiang Zhang; Xi Chen; Lin Wang (Science Bulletin, 2026)

The domestication-associated WHP10 tandem cluster of amino acid transporter genes enhances whole-plant protein accumulation in maize - Wenhao Li; Youliang Li; Xiang Lin; Ruilin Chen; Wenjing Li; Chong You; Di Chen; Lulu Gao; Xiaoling Li; Shiqi Luo; Yunlong Li; Yuhua Long; et al. (Molecular Plant, 2026)

VcNADP-ME4 positively regulates malic acid degradation in blueberry fruit as modulated by two bZIPs - Yongfang Dai; Yi Min; Yuxin Leng; Miao Zhou; Huiying Chong; Lei Peng; Xiaoya Zheng; Lin Wang; Guangqin Wen; Xiaopeng Wen (Journal of Plant Physiology, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Engineering selenium-doped carbon dots as a high-performance ECL emitter for dual-mode sensing of p53 in vitro and in living cells - Jingshuo Jiang; Jie Song; Yang Liu; Chong Wang; Shanshan Wu; Subin Wei; Shihan Lin; Chao Wang; Jing chen; Pengfei Wei; Ningning Wang (Chemical Engineering Journal, 2026)

ε-poly-l-lysine–grafted nanocellulose prepared by enzymatic oxidation for high-internal-phase Pickering emulsions and nutraceutical delivery - Huangjingyi Chen; Yujun Zou; Chong Tang; Qingyang Lin; Jie Wu; Orlando J. Rojas; Yimin Fan (Carbohydrate Polymers, 2026)

An online hierarchical path planning method for morphological and ecological observation of polar icebergs - Zhuo Wang; Lin Zhou; Nan Zhou; Zhongchao Deng; Zhongben Zhu; Yifan Xue; Hongde Qin; Guiqiang Bai; Chong Wang (Ocean Engineering, 2026)

Solvent effects on quercetin incorporation, release behavior, and antibacterial efficacy in gelatin/dialdehyde cellulose composite films: A comparative study - Myat Noe Khin; Shabbir Ahammed; Chong Yuen Yuen; Tariq Aziz; Maryam M. Alomran; Ashwag Shami; Fahad Al-Asmari; Maher S. Alwethaynani; Lin Lin (Food Hydrocolloids, 2026)

The effective adsorption of cobalt from radioactive wastewater by sulfonated g-C3N4 - Yusen Liu; Sinan Chen; Yifan Li; Xiangyi Du; Zhiyi Wang; Xiumei Wang; Hanbao Chong; Mingzhang Lin (Annals of Nuclear Energy, 2026)

Landscape composition and soil properties shape Monolepta hieroglyphica abundance in maize field of northern China's agro-pastoral ecotone - Hainan Chong; Yinghao He; Zeyang Guo; Peng Zhang; Haikuo Zhang; Chulei Xue; Jinyan Liu; Kejian Lin; Haijun Xiao (Agriculture, Ecosystems & Environment, 2026)

Graphite-engineered tungsten microneedle sensor for ultra-wide range nitrite detection - Xuexia Lin; Kunmeng Zhao; Zhilong Zhou; Fangqi Zhang; Huiting Lian; Chong-Chen Wang (Journal of Hazardous Materials, 2026)

A chlorine-rich argyrodite electrolyte with cost-effectiveness and high ionic conductivity for all-solid-state lithium batteries - Shijie Yu; Lin Zheng; Manzhen Fang; Linping Liao; Ting Yang; Peidian Chong; Yafeng Li; Longyuan Guo; Mingdeng Wei (Chemical Engineering Journal, 2026)

Corrigendum to “Large old trees sustain avian communities and critical plant-bird interactions in highly urbanised environments” [Biological Conservation 313 (2026) 111582] - Lin Xie; Xiao Huang; Tianhao Xia; Lan Wu; Si-Chong Chen (Biological Conservation, 2026)

Characterization, expression and evolution analysis of NLRC3 , NLRC5 and NLRX1 in Mastacembelus armatus under Aeromonas veronii infection - Shengyue Lin; Kaifeng Wang; Weijian Chen; Ziyan Deng; Guojun Cai; Min Zhang; Zihang Xie; Weibin Li; Chong Han; Qiang Li (Journal of Fish Biology, 2026)
NOD‐like receptors (NLRs) serve as crucial innate immune sensors in multicellular organisms, recognizing diverse pathogen‐associated components and regulating immune responses such as nuclear factor kappa B (NF‐κB) signalling and inflammatory pathways. To elucidate the roles of NLRC3 , NLRC5 and NLRX1 in the innate immunity of the Mastacembelus armatus , this study first characterized these genes and examined their response to Aeromonas veronii infection. We identified the three NLR genes from the M. armatus transcriptome and analysed their evolutionary relationships through domain architecture and maximum likelihood (ML) phylogenetic reconstruction. All three NLR proteins contained conserved NACHT and leucine‐rich repeat (LRR) domains, and ML phylogenetic analysis grouped M. armatus with other Synbranchiformes and Perciformes, consistent with established taxonomy. Tissue expression profiling in healthy fish revealed constitutive expression of all three genes across nine examined tissues, with significantly higher levels in gills, suggesting their involvement in frontline mucosal immunity. Temporal expression analysis in spleen, liver and kidney following A. veronii challenge showed distinct organ‐specific patterns: although all three genes were downregulated in the liver, they were significantly upregulated in spleen and kidney, indicating these as primary sites for NLR‐mediated immune responses in M. armatus . Selection pressure analysis using CodeML identified widespread purifying selection across teleost NLRs, alongside multiple positively selected sites in NLRC5 (7 sites in site model, 5 in branch‐site model) and NLRX1 (2 sites in site model, 22 in branch‐site model). These findings provide fundamental insights into NLR‐mediated immunity in M. armatus and contribute to understanding the evolution and function of NLR genes in teleosts.

Global inland waters trophic status from space observation: scientific advances and future challenges - Lili Lyu; Pierre-Andre Jacinthe; Nan Lin; Dongmei Lyu; Ge Liu; Sijia Li; Chong Fang; Hui Tao; Hao Yu; Zuchuan Li; Kaishan Song (Water Research, 2026)

Round-ended concrete-filled FRP tubes subjected to monotonic axial compression: Experimental study and design-oriented model - Bing Zhang; Yunhao Yan; Guan Lin; Yutao Peng; Chong Zhou (Engineering Structures, 2026)

A data informativeness evaluation method for grey-box modeling of building thermal dynamics - Xinyi Lin; Zhe Tian; Adrian Chong; Yakai Lu; Jide Niu; Na Deng (Energy and Buildings, 2026)

Stable yet hydrophilic graphene oxide nanomembranes by zwitterionic reduction for dye desalination - Sagnik Das; Ziwen Zhang; Erda Deng; Emmanuel M. Nsengiyumva; Ruveen Dias; Shixian Ha; Xiao Tong; Gbassey S.A. Oteme; Shweta Singh; Kai Chen; Prathima C. Nalam; Chang-Yong Nam; et al. (Chemical Engineering Journal, 2026)

Benchmarking and lightweight correction of daily near-surface air temperature products over the Qinghai-Tibetan Plateau - Nan Zhou; Yao Xiao; Lin Zhao; Guojie Hu; Lingxiao Wang; Chong Wang; Ren Li; Guangyue Liu; Defu Zou; Xiangfei Li (Atmospheric Research, 2026)

A simplified RUBY reporter-enabled hairy-root system for rapid evaluation of genome editing and gene function in grapevine - Chong Ren; Yanping Lin; Mohamed Salaheldin Mokhtar Mohamed; Chencong Liu; Zhenchang Liang (Planta, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Dietary D-mannose maintains intestinal microbiota balance and alleviates dextrose sodium sulfate (DSS)-induced enteritis of juvenile grass carp (Ctenopharyngodon idella) - Chong Zhang; Lin Feng; Pei Wu; Yang Liu; Xiaowan Jin; Hongmei Ren; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2026)

Highly effective masculinization of mandarin fish (Siniperca chuatsi) using Etonogestrel: A practical method for aquaculture and transcriptomic mechanism elucidation - Jiangwei Zhou; Simin Zhong; Shengyue Lin; Shuzheng Ye; Dingxian Chen; Chong Han; Qiang Li (Aquaculture, 2026)

Lessons learned from shield machine penetrating beneath the existing diaphragm walls using artificial ground freezing (AGF) - Yu-Yong Jiao; Jian-Feng Qi; Xue-Feng Yan; Lin-Chong Huang; Qian-Bing Zhang (Tunnelling and Underground Space Technology, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

High-resolution (30 m) mapping of permafrost distribution in the Genhe River Basin, Greater Khingan Mountains, Northeast China - Xueling Jiao; Lin Zhao; Defu Zou; Lingxiao Wang; Chong Wang; Yuanwei Wang; Guojie Hu; Erji Du; Yao Xiao; Guangyue Liu; Shibo Liu; Yuxin Zhang; et al. (Journal of Mountain Science, 2026)

On-exosome-membrane DNA polymerization-powered magneto-electrochemical aptasensing for osteosarcoma - Guang-Xian Zhong; Huang-Feng Lin; Fei-Huan Fu; Jing-Wei Zhou; Chong-Yu Chen; Chao-Yang Wu; Jian-Ping Lin; Xiong-Wei Xu; Jian-Hua Lin; Jin-Yuan Chen (Analytica Chimica Acta, 2026)

Construction of 3D printable native-modified corn starch composites gels as dysphagia diet: Crucial role of modified starch - Jiangkai Zeng; Yumin Duan; Zaifei Zheng; Peng Wang; Xiaoqi Ma; Lin Wang; Chong Cui; Bo Bo; Xiaoshuai Yu; Zhigang Xiao (Food Research International, 2026)

Evaluation of stability and cooling engineering effectiveness of the Qinghai-Tibet transportation routes: A first comprehensive assessment using space geodetic observations - Lingxiao Wang; Lin Zhao; Shibo Liu; Huayun Zhou; Guojie Hu; Defu Zou; Erji Du; Guangyue Liu; Yao Xiao; Yueli Chen; Jianting Zhao; Wei Chen; et al. (Engineering Geology, 2026)

Undescribed dihydro- β -agarofuran sesquiterpenoids from the roots of Tripterygium wilfordii - Ya-Lin Hu; Jia-Li Huang; Chong Wang; Wen-Jie Chen; Jing-Yi Huang; Yi-Ping Xie (Natural Product Research, 2026)

Human-induced changes in fluvial regimes for organic carbon supply and burial off the Yellow River Estuary - Li Jiang; Limin Hu; Naishuang Bi; Jinya Xu; Jun Ye; Lin Liu; Fudong Lin; Weini Chong; Jiazong Du; Xiao Wu; Houjie Wang (Water Research, 2026)

Copper overload induces lifespan shortening through activating mitochondrial respiration in Caenorhabditis elegans - Jia Zhang; Chang Liu; Yuxin Liao; Wanqiao He; Yantao Zheng; Hao Shi; Qiong Liu; Jiajie Lin; Chong Gao; Xuanbin Wang; Lei Gao (Journal of Hazardous Materials, 2026)

Investigation on the heating performance of an ultra-low temperature air source heat pump system - Chongchong Hou; Chong Han; Hui Yan; Musen Lin; Long Ni (Energy and Buildings, 2026)

Novel senescence inducer ICA-11c, a derivative of icaritin, YAP-dependently suppresses hepatocellular carcinoma cells - Hong-fei Chen; Shuai Shen; Shuang-li Wang; Li Ye; Ji-chong Li; Wen-li Cao; Zi-lin Hou; Jian-huan Jia; Qing-bo Liu; Guo-dong Yao; Shao-jiang Song (Chemico-Biological Interactions, 2026)

Large old trees sustain avian communities and critical plant-bird interactions in highly urbanised environments - Lin Xie; Xiao Huang; Tianhao Xia; Lan Wu; Si-Chong Chen (Biological Conservation, 2026)

Spatial distribution of vegetation type in the Genhe River Basin based on multi-source data - Zhinan Zhou; Chong Wang; Lin Zhao; Defu Zou; Guangyue Liu; Shibo Liu; Lingxiao Wang; Guojie Hu; Zanpin Xing; Erji Du; Yao Xiao; Xueling Jiao (International Journal of Remote Sensing, 2025)

Perinatal maternal lead exposure induces intergenerational neurotoxicity via mitochondrial dysfunction and mediation by perturbation of thyroid function - Lin Zhang; An-Xin Lu; Ling Li; Qian Wei; Yin Lin; Jun-Xia Liu; Li Ma; Ren-Tong Chen; Bin Luo; Chong-Huai Yan (Journal of Hazardous Materials, 2025)

Trigger efficient peroxydisulfate-assisted photocatalysis by S-scheme Co3O4/BiOCl heterojunctions: Vital roles of Co2+/Co3+ redox centers and oxygen vacancies - Chang-Bin Yu; Chong Xu; Lin He; Wei-Ya Huang; Kai Yang; Dan Li (Journal of Environmental Chemical Engineering, 2025)

Seismic performance of precast concrete shear wall with disc spring-bolt subassembly connections - Hua-long LIU; Xun CHONG; Lin-lin XIE; Qing JIANG; Yu-long FENG; Jun-Qi HUANG (Engineering Structures, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Triple-pronged strategy: A theranostic hydrogel platform with near-infrared chemiluminescence imaging-guided sonodynamic therapy for bacterial-infected wound healing - Jiaxin Yang; Kaijia Lin; Ke Xu; Liping Zhang; Qian Zhang; Gelin Xu; Yachao Wang; Haixing Feng; Yayun Xu; Yanqin Fan; Ziwei Wang; Zihan Wu; et al. (Chemical Engineering Journal, 2025)

Morphological, histological and multi-omics analysis revealed the molecular response of female western mosquitofish (Gambusia affinis) to levonorgestrel exposure - Kaichun Chen; Tongfu Lu; Weijian Chen; Shengyue Lin; Dingxian Chen; Shuzheng Ye; Weiqian Liang; Sixun Li; Binhua Deng; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Unraveling the potential mechanism and prognostic value of pentose phosphate pathway in hepatocellular carcinoma: a comprehensive analysis integrating bulk transcriptomics and single-cell sequencing data - Bin Li; Tao Zeng; Cui Chen; Yuankai Wu; Shuying Huang; Jing Deng; Jiahui Pang; Xiang Cai; Yuxi Lin; Yina Sun; Yutian Chong; Xinhua Li; et al. (Functional & Integrative Genomics, 2025)

Implementation of memristive emotion associative learning circuit - Zhangzhi Zhou; Mi Lin; Xuanxuan Zhou; Chong Zhang (Cognitive Neurodynamics, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Late Holocene extreme dust events in the arid Central Asia recorded by lake sediments in Tien Shan - Min Zheng; Xiaozhong Huang; Ning Wang; Menghan Qiu; Jun Zhang; Lixiong Xiang; Shaojun Chen; Muhammad Farqan; Ruiqi Min; Tao Wang; Chong Huang; Xiuxiu Ren; et al. (Quaternary Science Reviews, 2025)

Quantifying the soil water content of the permafrost active layer using InSAR deformation - Erji Du; Lingxiao Wang; Lin Zhao; Huayun Zhou; Shibo Liu; Defu Zou; Guangyue Liu; Yao Xiao; Guojie Hu; Zhibin Li; Junqiang Gao; Chong Wang; et al. (Journal of Hydrology, 2025)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Entropy-stabilized multi-element 2D TMDs: Tunable electronics and enhanced thermal stability - Ching-Wei Chin; Chong-Chi Chi; Kai-Yuan Hsiao; Yi-Hsin Fang; Dun-Jie Jhan; Chun-Hui Lin; Ming-Pei Lu; Ming-Yen Lu (Chemical Engineering Journal, 2025)

Meta-analysis and empirical research on the effectiveness of biochar in remediating tetracyclines pollution in water bodies - Na Li; Xiaochen Zhu; Yahui Miao; Zhenyao Wang; Carol Sze Ki Lin; Chong Li (Bioresource Technology, 2025)

Technical, economic and environmental evaluation of the hybrid renewable energy power system under different loads in the severe cold region of China - Chong Li; Lin Zhang; Xuemin Zhong (Clean Technologies and Environmental Policy, 2025)

Effects of compound probiotics on intestinal and liver transcriptome, immunity and disease resistance of zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Yiman Chen; Zhiting Zuo; Xianshan Lin; Qiaoyi Chen; Along Gao; Zhide Yu; Chong Han; Hu Shu (Aquaculture, 2025)

Exploring controls on precipitation-runoff dependencies: Implications for non-stationary and spatially heterogeneous analyses - Tian Lan; Xinyue Du; Xue Xie; Kairong Lin; Hongbo Zhang; Xinghui Gong; Yongqin David Chen; Chong-Yu Xu (Journal of Hydrology, 2025)

Facilitating extensive CC bond cleavage in lignin models through customized CeO2/C3N4 S-scheme heterojunction - Hongwu Liao; Chong Wang; Jiaxian Zheng; Zhuo Chen; Yulin Zhou; Chengning Ye; Xiangfeng Lin; Meng An; Yusuke Yamauchi; Yusuke Asakura; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Levonorgestrel-induced anal fin masculinization in mosquitofish: Do TGF-β/BMP signaling and osteogenic remodeling underpin endocrine disruption in aquatic ecosystem? - Weiqian Liang; Tongfu Lu; Dingxian Chen; Weijian Chen; Kaifeng Wang; Jie Lai; Shengyue Lin; Lin Gui; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Threshold-governed insulating and cooling effects of snow cover on alpine permafrost: evidence from the Qinghai–Tibet Plateau - Yao Xiao; Guojie Hu; Ren Li; Tonghua Wu; Xiaodong Wu; Guangyue Liu; Defu Zou; Zanpin Xing; Jimin Yao; Chong Wang; Lin Zhao (Agricultural and Forest Meteorology, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Enhancing high-temperature phase stability and thermal properties of 5RE(TaxNb1-x)O4 high-entropy ceramics through chemical bonding strength optimization - Mengdi Gan; Liping Lai; Xiaoyu Chong; Qianqian Jin; Wei Yu; Jiankun Wang; Jun Wang; Lin Chen; Jingjin He; Jing Feng (Chemical Engineering Journal, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

A matrix for estimating the unfrozen water content of freezing soils - Jun Bi; Guoxu Wang; Wenxuan Mu; Haiyan Wen; Wansheng Pei; Qiyong Zhang; Sheng Yang; Mengyao Mao; Gaochao Lin; Chong Wang (CATENA, 2025)

Recycling traditional Chinese medicine residues: a review - Xiaowei Wu; Dai Dai; Na Li; Haixin Zheng; Cuixia Wang; Weixiong Lin; Liaoyuan Liu; Zheng Zhang; Jörg Rinklebe; Carol Sze Ki Lin; Wen Rui; Chong Li (Environmental Chemistry Letters, 2025)
Traditional Chinese medicine has a rich history in the diagnosis and treatment of diseases, yet the disposal of medicine residues by incineration and landfilling is challenging. Here we review methods to recycle Chinese medicine residues with focus on challenges, recycling solutions, and case studies. Cases studies include extraction of bioactive compounds, use as feed additives, and biochar-based materials. We observed that residues from single-compound medicines are easier to extract and recycle into animal feed additives or adsorbents. Technical and economic analysis show that the valorisation of single-compound medicine residues is profitable. For instance, the re-extraction cost of flavonoids is 25.8–36.6% lower than the market price, and the cost as feed additives represents 14.7% of the market prices.

Response and recovery times of vegetation productivity under drought stress: Dominant factors and relationships - Chengyun Wang; Jie Chen; Sung-Ching Lee; Lihua Xiong; Tianhua Su; Qian Lin; Chong-Yu Xu (Journal of Hydrology, 2025)

A Novel Metric for Assessing Long-Term Outcomes in Adults with Chiari Malformation Type I: Occipitocervical Dura Angulation (ODA)—Applications and Value - Bo Wang; Shi-Chao Chen; Yao-Wu Zhang; Wei-Hao Liu; Chong Wang; Yi-Xiang Liu; Guang-Hao Zheng; Jia-Lin Li; Kai Ji; Jun Yang; Yong-Zhi Wang; Wen-Qing Jia (The Cerebellum, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Lipid-lowering drug clofibric acid promotes conjugative transfer of RP4 plasmid carrying antibiotic resistance genes by multiple mechanisms - Lin Ding; Chong-Miao Zhang; Hong-Yu Jiang (Journal of Hazardous Materials, 2025)

Thiol-functionalized graphene oxide as superior adsorbent for highly efficiency removal of radioactive cobalt from wastewater - Yusen Liu; Qiqi Guo; Yifan Li; Xiangyi Du; Sinan Chen; Zhiyi Wang; Hanbao Chong; Mingzhang Lin (Journal of Environmental Chemical Engineering, 2025)

Fabrication of sweet potato leaf-derived nanocellulose and its influence on the properties and interactions in peanut protein films - Ming-yang Sun; Yu-qi Yang; Qi Gao; Jia-nan Chen; Chong-ting Guo; Miao Yu; Jia-jia Rao; Xue-jun Gu; You-lin Xue (Food Hydrocolloids, 2025)

Isotopic Analysis for Tracing Vertical Growth Trajectories of Hailstones - Xiangyu Lin; Haifan Zhang; Xiaofei Li; Qinghong Zhang; Andrew Heymsfield; Kai Bi; Chan-Pang Ng; Chong Wu; Dianli Gong (Advances in Atmospheric Sciences, 2025)

Understanding tractography in edematous brain regions: challenges and solutions - Shin Tai Chong; Joseph Yuan-Mou Yang; Ching-Po Lin (Brain Structure and Function, 2025)

Association of cold weather and influenza infection with stroke: a 22-year time-series analysis - Zihan Yang; Yuchen Wei; Xiaoting Jiang; Conglu Li; Guozhang Lin; Yawen Wang; Ka Chun Chong (International Journal of Biometeorology, 2025)
Despite the significant adverse health effects and economic burden of stroke inpatients, there has been a paucity of research specifically analyzing and quantifying the association between meteorological factors, air pollutants, influenza infection, and stroke admissions. This study assessed the impact of environmental factors and influenza activity on stroke admissions in Hong Kong from 1998 to 2019, utilizing population-based records. We employed the number of weekly stroke admissions as the primary outcome measure and matched the number with meteorological factors and air pollutant concentrations. Strain-specific influenza-like illness-positive (ILI+) rates were used as a proxy indicator of influenza activity. A quasi-Poisson generalized additive model in combination with a distributed-lag non-linear model (DLNM) was employed to elucidate the relationship of interest. Over the 22-year period, a total of 1,170,882 stroke-related admissions were recorded in Hong Kong. The cumulative adjusted relative risk (ARR) of stroke admission was significantly increased (cumulative ARR = 1.106, 95% CI, 1.069–1.143) at the 5th percentile of temperature (i.e., 15.08 °C) compared with the median reference level. Using zero as the reference value, the cumulative adjusted relative risks of stroke admission were 1.030 (95% CI, 1.018–1.042) at the 95th percentile of ILI + A/H1N1 rate, and 1.022 (95% CI, 1.007–1.038) at the 95th percentile of ILI + total rate. In conclusion, cold weather and influenza infection are risk factors to stroke admissions. Public health strategies for preventing stroke should be considered such as advocating influenza vaccination programmes during winter.

Temporal trend of organic carbon in the East Siberian Arctic shelf sediments and its relation to the recent climate forcing - Jialong Luo; Li Jiang; Limin Hu; Zenghui Yu; Weini Chong; Fudong Lin; Fenghua Su; Yanguang Liu; Kirill Aksentov; Alexander Bosin; Anatolii Astakhov; Xuefa Shi (Acta Oceanologica Sinica, 2025)

Analytical method for laterally loaded offshore slender piles near sandy slopes considering slope deformation - Chong Jiang; Maolin Sun; Pan Liu; Mingke Lin; Jing Liu (Marine Georesources & Geotechnology, 2025)

Retrieval of 1 km surface soil moisture from Sentinel-1 over bare soil and grassland on the Qinghai-Tibetan Plateau - Zanpin Xing; Lin Zhao; Lei Fan; Gabrielle De Lannoy; Xiaojing Bai; Xiangzhuo Liu; Jian Peng; Frédéric Frappart; Kun Yang; Xin Li; Zhilan Zhou; Xiaojun Li; et al. (Remote Sensing of Environment, 2025)

Mutation in FvPAL2 leads to light red strawberry fruits and yellow-green petioles - Chong Wang; Anqi Lin; Yankong Zhou; Zheng Liu; Peng Bai; Yuxuan Zhu; Junmiao Fan; Xiaoyi Bi; Huiyun Kuang; Hongli Lian; Pengbo Xu (Plant Science, 2025)

Fatigue fracture and energy evolution characteristics of sandstone under water–ice phase transitions via the discrete element method - Zhidan Zheng; Zhanming Shi; Mengxiang Wang; Hang Lin; Jiangteng Li; Dongya Han; Kaihui Li; Chong Jiang (Computers and Geotechnics, 2025)

Brems1 mutation induced tapetum deficiency leading to male sterility in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Chuanhong Liu; Lin Wang; Chong Tan; Di Zhao; Zhiyong Liu (Theoretical and Applied Genetics, 2025)

Study on Connectivity of Fractured-Vuggy Marine Carbonate Reservoirs Based on Dynamic and Static Methods - Yintao Zhang; Chengyan Lin; Lihua Ren; Chong Sun; Jing Li; Zhicheng Wang; Guojin Xu (Journal of Marine Science and Engineering, 2025)
Fractured-vuggy marine carbonate reservoirs, as an unconventional energy resource, hold significant potential for exploration and development. In this study, the Manshen block of the Furman oilfield in the Tarim Basin, China, was selected as the research object. A systematic investigation was conducted on the types of marine carbonate reservoir bodies, production characteristics, and both static and dynamic connectivity. Static connectivity analysis was performed using the heat diffusion equation and the multi-source potential field method. Dynamic connectivity evaluation was carried out by combining the dynamic time warping (DTW) algorithm with the analytic hierarchy process (AHP). Well logging, core analysis, and cast-thin section experiments were utilized to determine the types of reservoir spaces. The results indicate that the main types of reservoir spaces in the study area are caves, pores, and fractures. The fractures are primarily structural, with secondary development of dissolution fractures, weathering fractures, and sutures. The productivity changes in oil wells in the study area are classified into three types: slow decline, rapid decline, and high-speed decline. Based on the connectivity coefficients, wells were divided into three connectivity groups, with the A32 well group having the highest connectivity, followed by B5 well group 1, and B5 well group 2 having the lowest connectivity. The research provides technical support for the accurate evaluation of marine carbonate reservoirs and contributes to enhancing the efficiency of oil and gas exploration and development.

Effective denitrification from landfill leachate using magnetic PVA/CMC/DE carrier immobilized microorganisms - Yunshuang Hu; Yufei Gu; Jiahui Tan; Chong Ding; Xinyi Yu; Zhixia Li; Hongfei Lin (Waste Management, 2025)

Impact of aerosol-photolysis interaction on the ozone concentration in the upper boundary layer on Mountain Everest - Yi Chen; Gang Zhao; Chunxiang Ye; Weili Lin; Chong Zhang; Jiacheng Zhou; Jing Gao; Tong Zhu (Science of The Total Environment, 2025)

Theoretical estimations of carbon geological storage capacities in the deep aquifer in Songliao Basin: Insights from spatial stochastic simulation - Zhijian Sun; Lin Zhang; Wanli Xue; Chong Zhang; Hongbin Zhan; Yanfeng Liu (Journal of Environmental Management, 2025)

Volatile organic compounds at a highland forest site in the southeast of the Tibetan Plateau: Source apportionment and reactivity contributions - Shuzheng Guo; Chunxiang Ye; Weili Lin; Yi Chen; Limin Zeng; Xuena Yu; Jinhui Cui; Chong Zhang (Environmental Pollution, 2025)

Scalable thin graphene oxide membranes enabled by polydopamine gutter layer - Ameya Manoj Tandel; Sagnik Das; Chong Cheng; Haiqing Lin (Chemical Engineering Journal, 2025)

The relationship between indoor airborne culturable bacteria with passenger flow in 132 traffic stations during 2019–2020, China - Li Li; Hang Du; Chong Meng; Lin Fan; Hang Liu; Xu Han; Tanxi Ge; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2025)

Predicting the efficiency of arsenic immobilization in soils by biochar using machine learning - Jin-Man Cao; Yu-Qian Liu; Yan-Qing Liu; Shu-Dan Xue; Hai-Hong Xiong; Chong-Lin Xu; Qi Xu; Gui-Lan Duan (Journal of Environmental Sciences, 2025)

Pitfalls in measuring solution toxicity using the level of bioluminescence inhibition in Aliivibrio fischeri - Cheng-Kun He; Ming-Chun Hung; Chong-Hao Hxu; Yi-Hsien Hsieh; Yung-Sheng Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

On the multiscale processes leading to three heavy rainfall episodes over beijing and its periphery in july 2016 - Rudi Xia; Chong Wu; Da-Lin Zhang; Yali Luo; Jinfang Yin (Meteorology and Atmospheric Physics, 2025)

Nonlinear seismic performance of offshore wind turbines on hybrid pile-bucket foundation in sand: Combined earthquake and wind-wave loads - Wei-Yun Chen; Yu-Jie Jiang; Lin-Chong Huang; Ling-Yu Xu; Chao Liu; Guo-Xing Chen (Soil Dynamics and Earthquake Engineering, 2024)

The dynamic adjusted system of sea use fees: An empirical research on the sea use management in Zhejiang province - Guanqiong Ye; Zeben Lian; Chong Chen; Chunyu Lin; Zhiguo He; Weidong Shang; Yongchao Zheng (Regional Studies in Marine Science, 2024)

Spaceborne high-spectral-resolution lidar ACDL/DQ-1 measurements of the particulate backscatter coefficient in the global ocean - Yichen Yang; Yudi Zhou; Iwona S. Stachlewska; Yongxiang Hu; Xiaomei Lu; Weibiao Chen; Jiqiao Liu; Wenbo Sun; Suhui Yang; Yuting Tao; Lei Lin; Weige Lv; et al. (Remote Sensing of Environment, 2024)

Enhancing exergy and economical performance of a waste heat power generation system: Multi-objective optimization and comparative analysis - Zhonglan Hou; Ismail Imechoui; Perk Lin Chong; Pengyan Guo; Yanli Deng; Yuguo Gao (Journal of Cleaner Production, 2024)

Complementarity and competitive trade-offs enhance forage productivity, nutritive balance, land and water use, and economics in legume-grass intercropping - Chong Liang Luo; Hai Xia Duan; Ya Lin Wang; Hong Jin Liu; Shi Xiao Xu (Field Crops Research, 2024)

Settling and rising velocities of microplastics: Laboratory experiments and lattice Boltzmann modeling - Xiaoteng Shen; Mingze Lin; Haoyu Chong; Jinfeng Zhang; Xiaorong Li; Peter Robins; Qilong Bi; Yuliang Zhu; Ying Zhang; Qiqing Chen (Environmental Pollution, 2024)

Contact-electro-luminescence triggered by triboelectric charge - Chong Xu; Shaoxin Li; Zhe Yang; Morten Willatzen; Zhong Lin Wang; Di Wei (Chemical Engineering Journal, 2024)

Transcriptome sequencing promotes insights on the molecular mechanism of SKP-SC-EVs mitigating denervation-induced muscle atrophy - Junfei Lin; Yong Cai; Jian Wang; Ruiqi Liu; Chong Qiu; Yan Huang; Boya Liu; Xiaoming Yang; Songlin Zhou; Yuntian Shen; Wei Wang; Jianwei Zhu (Molecular Biology Reports, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

Spray-on electronic tattoos with MXene and liquid metal nanocomposites - Lin Wang; Yong Lin; Cheng Yang; Qian Wang; Ting Fang; Chong Bai; Jianhui Wang; Desheng Kong (Chemical Engineering Journal, 2024)

Design of high-efficiency carbonic anhydrase mimics with well-defined Zn sites based on salphen organic framework - Lin Li; Wenjie Xu; Mao Wang; Shuang Li; Shudong Sun; Chong Cheng; Changsheng Zhao (Chemical Engineering Journal, 2024)

Cuproptosis in microsatellite stable colon cancer cells affects the cytotoxicity of CD8+T through the WNT signaling pathway - Jintao Zeng; Hong Chen; Xing Liu; Haoyun Xia; Liqi Chen; Dajia Lin; Naisen Wang; Chong Weng; Guoxian Guan; Yu Zheng (Chemico-Biological Interactions, 2024)

The Roles of Micro Pores and Minerals in Shale during Hydraulic Fracturing - Chong Lin; Xufei Jia; Shuowen Deng; Jincheng Mao; Xueyong Chen; Jianming He; Xiao Li (Rock Mechanics and Rock Engineering, 2024)

Ozone production sensitivity in the highland city of Lhasa: a comparative analysis with Beijing - Yi Chen; Suzhen Chi; Yaru Wang; Shuzheng Guo; Chong Zhang; Chunxiang Ye; Weili Lin (Air Quality, Atmosphere & Health, 2024)

Elevated Serum Magnesium Levels May Delay the Loss of Residual Renal Function among Patients Receiving Peritoneal Dialysis: A Prospective Study - Jing Zhao; Xuechun Lin; Jinxue Wang; Xiaolei Guo; Fan Peng; Xuezhi Zuo; Chong Tian; Chenjiang Ying (Biological Trace Element Research, 2024)

Evaluating soil freezing characteristic curve models for predicting unfrozen water content in freezing soils - Fanshuo Meng; Qian Chen; Jun Du; Yumo Wu; Zhikun Lin; Jiaqi Tian; Chong Wang (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Unraveling the mechanism of selective dissolution in anthracite coal for enhanced permeability through sodium hypochlorite oxidation treatment - Yu Lu; Yili Kang; Zhigang Li; Ming Yue; Teng Zhang; Feng He; Chong Lin; Yue Hu; Ying Li; Zhenjiang You (Fuel, 2024)

Sustainable management and valorization of antibiotic waste - Md Ariful Haque; Lindsay Rogerson; Nirmalendu Deb Nath; Samuel Haruna; Jaehyun Ahn; Tony V. Johnston; Carol Sze Ki Lin; Li Chong; Li Na; Min Ji Jang; Seockmo Ku (Chemical Engineering Journal, 2024)

Hollow tubular MnOx prepared by flame annealing with cotton fiber as sacrificial template and its applications for Hg0 adsorption in flue gas - Shengyan Liu; Wensheng Lin; Ao Wang; Wei Chen; Liangying Yu; Chong Tian (Chemical Engineering Journal, 2024)

Predicting frost heave in soil-water systems using the generalized regression neural network optimized with particle swarm optimization algorithm - Honghong Cai; Chong Wang; Ziqiang Ma; Fanshuo Meng; Zhikun Lin; Junping Ren; Shuangyang Li (Cold Regions Science and Technology, 2024)

Greenhouse gas emissions and carbon and water footprints during processing of Lei bamboo shoots - Zixiang Weng; Shuiqin Lu; Xuekun Cheng; Chunyu Pan; Guangyu Wang; Dejin Dong; Zhengcai Li; Ziliang Zhao; Lei Gu; Linghui Dong; Zhengwen Niu; Chong Li; et al. (Journal of Cleaner Production, 2024)

Unlocking synergies of drawdown operation: Multi-objective optimization of reservoir emergency storage capacity - Shufei Li; Di Zhu; Fanqi Lin; Jun Xia; Yanlai Zhou; Fi-John Chang; Chong-Yu Xu (Journal of Environmental Management, 2024)

Analysis for the effect of scour on pile lateral behavior in sand under combined loads considering additional stress and coupling effect of lateral-vertical load - Mingke Lin; Chong Jiang (Computers and Geotechnics, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Effect of environmental exposome and influenza infection on febrile seizure in children over 22 years: a time series analysis - Xiaoting Jiang; Conglu Li; Qianying Yue; Yuchen Wei; Yawen Wang; Xiang Qian Lao; Guozhang Lin; Ka Chun Chong (International Journal of Biometeorology, 2024)
Febrile seizures are convulsions predominately occurring in young children. The effects of various exposomes, including influenza infection and external environmental factors, on febrile seizures have not been well-studied. In this study, we elucidated the relationships between ambient temperature, air pollutants, influenza infection, and febrile seizures using 22-year territory-wide hospitalization data in Hong Kong. The aggregated data were matched with the meteorological records and air pollutant concentrations. All-type and type-specific influenza-like illness positive (ILI+) rates were used as proxies for influenza activity. Distributed lag non-linear model in conjunction with the quasi-poisson generalized additive model was used to examine the associations of interest. According to the results, all-type influenza infections were significantly associated with an increased risk of hospital admissions for febrile seizures (cumulative adjusted relative risk [ARR] = 1.59 at 95th percentile vs. 0; 95% CI, 1.51–1.68). The effect of ILI + A/H3N2 on febrile seizure was more pronounced than other type-specific ILI + rates. A low mean ambient temperature was identified as a significant risk factor for febrile seizures (cumulative ARR = 1.50 at 5th percentile vs. median; 95% CI, 1.35–1.66), while the redox-weighted oxidant capacity and sulfur dioxide were not associated with febrile seizures. In conclusion, our study underscores that influenza infections and exposure to cold conditions were related to an increased risk of febrile seizures in children. Thus, we advocate for influenza vaccination before the onset of the cold season for children to mitigate the burden of febrile seizures.

Analysis of lateral bearing mechanism for offshore monopiles in sand and development of an analytical method - Pan Liu; Chong Jiang; Mingke Lin; Maolin Sun; Fanhuan Zeng (Ocean Engineering, 2024)

Influence of the natural makeup air system on the kitchen environment in low-energy buildings in severely cold regions - Jiqin Li; Lin Yu; Anqi Liu; Chong Meng; Yingchao Ma; Jiankai Dong (Building and Environment, 2024)

Daphmacrimines A−K, Daphniphyllum alkaloids from Daphniphyllum macropodum Miq - Li-Li Xu; Zhen-Peng Niu; Duo-Zhi Chen; Yu Zhang; Qian Zhao; Hong Liang; Sheng Li; Jin-Liang Li; Xiao Ding; Chong-Lin Yang; Xiao-Jiang Hao (Phytochemistry, 2024)

A conductive and anti-freezing gelatin-PAA-based organic hydrogel (PC-OH) with high adhesion and self-healing activities for wearable electronics - Zhenglin Chen; Jiaqi Yang; Zhicheng Du; Jiansong Ji; Likun Zhang; Haifei Guan; Zhengyang Lei; Xiaopeng Zhang; Canhui Yang; Ying Zhu; Qianhui Sun; Lulu Xu; et al. (Chemical Engineering Journal, 2024)

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

Strong adsorption enhanced nitrogen removal from landfill leachate by PVA/CMC/WPU pellets immobilized microorganisms - Jiahui Tan; Yunshuang Hu; Chong Ding; Yuyu Li; Yufei Gu; Zhixia Li; Hongfei Lin (Journal of Water Process Engineering, 2024)

Soil moisture dynamics and associated rainfall-runoff processes under different land uses and land covers in a humid mountainous watershed - Zhixin Lin; Qiang Wang; Youpeng Xu; Shuang Luo; Caiyu Zhou; Zhihui Yu; Chong-Yu Xu (Journal of Hydrology, 2024)

Late Triassic floras from Guangdong, South China: Biostratigraphical context and palaeoenvironmental implications - Xiaoqing Zhang; Yongdong Wang; Chong Dong; Xiaoming Lin; Jianhua Jin (Geobios, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Occurrence, ecotoxicity and ecological risks of psychoactive substances in surface waters - Lin Ding; Chong-Miao Zhang (Science of The Total Environment, 2024)

Optimizing the deployment of LID facilities on a campus-scale and assessing the benefits of comprehensive control in Sponge City - Xianbao Zha; Wei Fang; Wei Zhu; Shuangtao Wang; Yong Mu; Xiaofeng Wang; Pingping Luo; Mohd Remy Rozainy Mohd Arif Zainol; Mohd Hafiz Zawawi; Khai Lin Chong; Apip Apip (Journal of Hydrology, 2024)

Feasibility study of biodegradable coffee ground waste and watermelon rind as water-based drilling fluid additives - Chukwuemeka Madu; Foad Faraji; Mardin Abdalqadir; Sina Rezaei Gomari; Perk Lin Chong (Gas Science and Engineering, 2024)

In vitro digestion mimicking conditions in adults and elderly reveals digestive characteristics of pork from different cooking ways - Xiangyue Cao; Fan Zhao; Ziyi Lin; Xiaomei Sun; Xianming Zeng; Haoxi Liu; Yutong Li; Zihang Yuan; Yuan Su; Chong Wang; Guanghong Zhou (Food Research International, 2024)

Microplastics in Asian rivers: Geographical distribution, most detected types, and inconsistency in methodologies - Hsin-Tien Lin; Falk Schneider; Muhamad Afiq Aziz; Keng Yinn Wong; Kantha D. Arunachalam; Sarva Mangala Praveena; Sumathi Sethupathi; Woon Chan Chong; Ayu Lana Nafisyah; Purushothaman Parthasarathy; Shreeshivadasan Chelliapan; Alexander Kunz (Environmental Pollution, 2024)

Optimizing a twin-chamber system for direct ozone production rate measurement - Yaru Wang; Yi Chen; Suzhen Chi; Jianshu Wang; Chong Zhang; Weili Lin; Weixiong Zhao; Chunxiang Ye (Environmental Pollution, 2024)

Observing glacial isostatic adjustment by PSInSAR in southern Hudson Bay - Chong-You Wang; Yunung Nina Lin; Cheinway Hwang; C K Shum (Remote Sensing of Environment, 2024)

Heteroatom doping-induced Pt dispersion and electronic effect for boosting the catalytic performance in the hydrogenation of nitrobenzene to p-aminophenol - Chong Yao; Jiwei Wu; Limei Pan; Lu Yu; Jie Luo; Jinjin Shan; Jie Liu; Chunshan Lu; Feng Feng; Xiaoliang Xu; Lili Lin; Yuxue Yue; et al. (Chemical Engineering Journal, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Trifluoperazine activates AMPK / mTOR / ULK1 signaling pathway to induce mitophagy in osteosarcoma cells - Wenhui Shen; Xiangchen Zeng; Xianhui Zeng; Baoshan Hu; Chong Ren; Zhiming Lin; Long Zhang; Gang Rui; Miersalijiang Yasen; Xiaohui Chen (Chemico-Biological Interactions, 2024)

Evaluating the Educational Value of Cancer Registries — a Systematic Review and Thematic Analysis - James Lin; Hugo C. Temperley; Kirsten Larkins; Caitlin Waters; Kit Loong Chong; Jack Maida; David Proud; Adele Burgess; Alexander Heriot; Philip Smart; Helen Mohan (Journal of Cancer Education, 2024)

METTL3-m6A-SIRT1 axis affects autophagic flux contributing to PM2.5-induced inhibition of testosterone production in Leydig cells - Lianlian Jiang; Xiaojun Lin; Jinchen Jiang; Chong Qiu; Shaokai Zheng; Nannan Zhao; Zhenhao Shu; Yinyun Qian; Lianglin Qiu (Science of The Total Environment, 2024)

Long-term (2003−2021) evolution trend of water quality in the Three Gorges Reservoir: An evaluation based on an enhanced water quality index - Chong Sang; Lu Tan; Qinghua Cai; Lin Ye (Science of The Total Environment, 2024)

FvDFR2 rather than FvDFR1 play key roles for anthocyanin synthesis in strawberry petioles - Xinyu Li; Xi Luo; Zhongchi Liu; Chong Wang; Anqi Lin; Kun Xiao; Minghao Cao; Junmiao Fan; Hongli Lian; Pengbo Xu (Plant Science, 2024)

Decarbonizing the energy supply chain: Ammonia as an energy carrier for renewable power systems - Chong Wei Ong; Nairen Chang; Meng-Lin Tsai; Cheng-Liang Chen (Fuel, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Machine learning methods for the modelling and optimisation of biogas production from anaerobic digestion: a review - Jordan Yao Xing Ling; Yi Jing Chan; Jia Win Chen; Daniel Jia Sheng Chong; Angelina Lin Li Tan; Senthil Kumar Arumugasamy; Phei Li Lau (Environmental Science and Pollution Research, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Permeability enhancement and coal fines removal through oxidation treatment in coalbed methane reservoirs - Yu Lu; Yili Kang; Chengzhong Bu; Ying Li; Chong Lin; Zhenjiang You (Fuel, 2024)

Structural design of Janus lamellar membrane based on bismuth oxychloride for comprehensive solar energy utilization - Weiming Zhou; Hongqiang Huang; Chong Wang; Liwei Wang; Xiangfeng Lin; Yusuke Asakura; Yusuke Yamauchi; Sameh M. Osman; Zhanhui Yuan (Chemical Engineering Journal, 2024)

Investigating the diurnal effects of on-street population and streetscape physical environment on street theft crime: A machine learning and negative binomial regression approach using street view images - Han Yue; Lin Liu; Chong Xu; Guangwen Song; Jianguo Chen; Li He; Lian Duan (Applied Geography, 2024)

Robust anti-perturbation safety control of multi-heterogeneous unmanned vessels - Yeye Liu; Xiaogong Lin; Yongchao Liu; Ziyi Su; Chong Liu (Ocean Engineering, 2024)

Study on the supercooling and crystallization mechanism of saline soil based on thermodynamic framework - Kunyu Li; Chong Wang; Yumo Wu; Zhikun Lin; Junping Ren; Juan Gao; Shuangyang Li (Journal of Hydrology, 2024)

The role of oxide supports in constructing plasma-treated gold nanocatalysts for visible light photocatalytic oxidation of CO - Bin Zhu; Chong-Hua Zhong; Bang-You Jia; Tie Li; Jing-Lin Liu; Ye-Cheng Li; Yi-Min Zhu (Chemical Engineering Journal, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Organic anion transporting polypeptide 3a1 is a novel influx pump for Perfluorooctane sulfonate in Sertoli cells and contributes to its reproductive toxicity - Ting Li; Lianlian Jiang; Shaokai Zheng; Chong Qiu; Nannan Zhao; Xiaojun Lin; Hang Ren; Jiyan Huang; Hongxia Wang; Lianglin Qiu (Chemosphere, 2023)

Isalo scorpion Cytotoxic peptide (IsCT) improved the physical barrier of the intestine on on-growing grass carp (Ctenopharyngodon idella) - Chong Zhang; Qi-Yu Hu; Lin Feng; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Jiang Li; Xiao-Qiu Zhou; Wei-Dan Jiang (Aquaculture, 2023)

Study on calculation method of lateral characteristics of offshore pile near layered soil slope - Chong Jiang; Mingke Lin; Pan Liu (Ocean Engineering, 2023)

Synthetic polymer fracturing fluid weighted by sodium formate enables fracture stimulations in Ultra-High pressure and High-Temperature reservoir - Xiaojiang Yang; An Chen; Jincheng Mao; Chong Zhang; Juanjuan Wang; Meitao Fu; Hu Zhang; Junjian Wang; Xianshi Song; Yang Zhang; Chong Lin (Fuel, 2023)

Fe2O3 nanosheet sacrificed templates for highly-permeable hollow fiber ultrafiltration membranes - Yuwei He; Chong Li; Zhen Lin; Qiugen Zhang (Chemical Engineering Journal, 2023)

Formation mechanism and quantitative risk analysis of the landslide-induced hazard chain by an integrated approach for emergency management: A case study in the Bailong River basin, China - Yan Chong; Guan Chen; Xingmin Meng; Shiqiang Bian; Fengchun Huang; Linxin Lin; Dongxia Yue; Yi Zhang; Fuyun Guo (CATENA, 2023)

Combining different ion-selective channelrhodopsins to control water flux by light - Fei Lin; Ruijing Tang; Chong Zhang; Nicole Scholz; Georg Nagel; Shiqiang Gao (Pflügers Archiv - European Journal of Physiology, 2023)
Water transport through water channels, aquaporins (AQPs), is vital for many physiological processes including epithelial fluid secretion, cell migration and adipocyte metabolism. Water flux through AQPs is driven by the osmotic gradient that results from concentration differences of solutes including ions. Here, we developed a novel optogenetic toolkit that combines the light-gated anion channel Gt ACR1 either with the light-gated K + channel Hc KCR1 or the new Na + channelrhodopsin Hc NCR1 with high Na + permeability, to manipulate water transport in Xenopus oocytes non-invasively. Water efflux through AQP was achieved by light-activating K + and Cl - efflux through Hc KCR1 and Gt ACR1. Contrarily, when Gt ACR1 was co-expressed with Hc NCR1, inward movement of Na + and Cl - was light-triggered, and the resulting osmotic gradient led to water influx through AQP1. In sum, we demonstrate a novel optogenetic strategy to manipulate water movement into or out of Xenopus oocytes non-invasively. This approach provides a new avenue to interfere with water homeostasis as a means to study related biological phenomena across cell types and organisms.

Expression of a periplasmic β-carbonic anhydrase (CA) gene is positively correlated with HCO3- utilization by the gametophytes of Saccharina japonica (Phaeophyceae, Ochrophyta) - Hui-Min Hao; Yan-Hui Bi; Ning-Ning Wei; Pei-Chong Lin; Shou-Hua Mei; Zhi-Gang Zhou (Journal of Applied Phycology, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Iodine status and associated dietary factors among preschool children in Shanghai - Jing Li; Jun-Xia Liu; Yu-Qing Wang; An-Xin Lu; Yi-Hong Wang; Yin Lin; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Exploring an intelligent adaptation method of hydrological model parameters for flood simulations based on the light gradient-boosting machine - Kangling Lin; Sheng Sheng; Hua Chen; Yanlai Zhou; Yuxuan Luo; Lihua Xiong; Shenglian Guo; Chong-Yu Xu (Journal of Hydrology, 2023)

Selective hydrocracking of poly-aromatics to mono-aromatics in a catalyst grading system of NiMo/Al2O3-HY and NiMo/Beta - Lin Qi; Chong Peng; Zhenmin Cheng; Zhiming Zhou (Fuel, 2023)

Effects of food-borne docosahexaenoic acid supplementation on bone lead mobilisation, mitochondrial function and serum metabolomics in pre-pregnancy lead-exposed lactating rats - An-Xin Lu; Yin Lin; Jing Li; Jun-Xia Liu; Chong-Huai Yan; Lin Zhang (Environmental Pollution, 2023)

Metabolomics insights into the effects of pre-pregnancy lead exposure on bone metabolism in pregnant rats - Lin Zhang; Yin Lin; An-Xin Lu; Jun-Xia Liu; Jing Li; Chong-Huai Yan (Environmental Pollution, 2023)

Active subduction and strain partitioning in western Myanmar revealed by a dense survey GNSS network - Eric O. Lindsey; Yu Wang; Lin Thu Aung; Jeng-Hann Chong; Qiang Qiu; Rishav Mallick; Lujia Feng; Pyae Sone Aung; Tha Zin Htet Tin; Saw Myat Min; Kyle Bradley; Oo Than; et al. (Earth and Planetary Science Letters, 2023)

Highly effective synthesis of 5-hydroxymethylfurfural from lignocellulosic biomass over a green and one-pot reaction in biphasic system - Quang Tam Huynh; Chong-Ting Zhong; Qing Huang; Yuan-Chung Lin; Ku-Fan Chen; Chien-Sen Liao; Cheng-Di Dong; Ken-Lin Chang (Bioresource Technology, 2023)

Methylmercury induced ferroptosis by interference of iron homeostasis and glutathione metabolism in CTX cells - Xi Xu; Su-Su Wang; Lin Zhang; An-Xin Lu; Yin Lin; Jun-Xia Liu; Chong-Huai Yan (Environmental Pollution, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

Association of air pollutants and meteorological factors with tuberculosis: a national multicenter ecological study in China - Qian Wang; Yan-lin Li; Ya-ling Yin; Bin Hu; Chong-chong Yu; Zhen-de Wang; Yu-hong Li; Chun-jie Xu; Yong-bin Wang (International Journal of Biometeorology, 2023)

Nanorod reassembling on a sprayed SERS substrate under confined evaporation inducing ultrasensitive TPhT detection - Lin Chang; Xiaohong Liu; Chong-Yew Lee; Wei Zhang (Analytica Chimica Acta, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Exploring a similarity search-based data-driven framework for multi-step-ahead flood forecasting - Kangling Lin; Hua Chen; Yanlai Zhou; Sheng Sheng; Yuxuan Luo; Shenglian Guo; Chong-Yu Xu (Science of The Total Environment, 2023)

Exploring a multi-output temporal convolutional network driven encoder-decoder framework for ammonia nitrogen forecasting - Sheng Sheng; Kangling Lin; Yanlai Zhou; Hua Chen; Yuxuan Luo; Shenglian Guo; Chong-Yu Xu (Journal of Environmental Management, 2023)

A novel framework to improve the consistency of water quality attribution from natural and anthropogenic factors - Shanlin Tong; Wenpan Li; Jie Chen; Rui Xia; Jingyu Lin; Yan Chen; Chong-Yu Xu (Journal of Environmental Management, 2023)

Higher impact resistance and lower antibiotic resistance genes proliferation rate in shortcut nitrification-denitrification process under long-term antibiotics selection pressure - Chong Yang; Zhouliang Tan; Lin Wang; Hongyan Zhang; Wenwei Li; Fan Wang; Xin Li; Houzhen Zhou; Yangwu Chen (Chemical Engineering Journal, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

A monitoring system for CO2-EOR and storage based on reactive transport simulation of CO2 migration in groundwater - L. Li; Y. Wu; Q. Lin; Q. Wen; S. Chong (International Journal of Environmental Science and Technology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Distribution of hydrogen isotope in the soil around the Qinshan Nuclear Power Plant - Jie Liang; Wen-yu Cheng; Jing-lin Li; Xiao-chong Xue; Ke Deng; Chao-fei Liang; Lin Du; Qin Zhang; Wei Liu (Journal of Environmental Radioactivity, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Multiple metal exposure and metabolic syndrome in elderly individuals: A case-control study in an active mining district, Northwest China - Sai Guo; Liting Hua; Wu Liu; Hongxiu Liu; Qiusheng Chen; Yongcheng Li; Xiaoxiao Li; Leicheng Zhao; Ruoqi Li; Zining Zhang; Chong Zhang; Lin Zhu; et al. (Chemosphere, 2023)

Selective catalytic reduction of NO with NH3 over MnOx-CeO2 catalysts: The great synergy between CeO2 and crystalline phase of Mn3O4 - Lijun Cheng; Songil Sin; Jiawei Ji; Shan Yang; Chong Tan; Zhiwen Gu; Wang Song; Chunkai Huang; Chuanzhi Sun; Changjin Tang; Lin Dong (Fuel, 2023)

Hierarchical phosphorus-oxygen incorporated cobalt sulfide hollow micro/nano-reactor for highly-efficient electrocatalytic overall water splitting - Ben Chong; Mengyang Xia; Yang Lv; He Li; Xiaoqing Yan; Bo Lin; Guidong Yang (Chemical Engineering Journal, 2023)

Levels, distribution, childhood exposure assessment, and influencing factors of polybrominated diphenyl ethers (PBDEs) in household dust from nine cities in China - Jing Qi; Xiaoli Wang; Lin Fan; Shuhan Gong; Xinqi Wang; Chong Wang; Li Li; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Performance of constructed wetlands with different water level for treating graphene oxide wastewater: Characteristics of plants and microorganisms - Chunni Yan; Juan Huang; Xiaoyang Lin; Yaoyao Wang; Chong Cao; Xiuwen Qian (Journal of Environmental Management, 2023)

Full-length transcriptome sequence and SSR marker development for genetic diversity research in yellowfin seabream Acanthopagrus latus - Jin Zhang; Jinmei Liu; Chong Han; Cheng Peng; Yong Li; Junhong Xia; Yong Zhang; Shuisheng Li; Haoran Lin (Journal of Oceanology and Limnology, 2023)

Chronic environmental inorganic arsenic exposure causes social behavioral changes in juvenile zebrafish (Danio rerio) - Yi-Hong Wang; Ya-Qian Wang; Xiao-Gang Yu; Yin Lin; Jun-Xia Liu; Wei-Ye Wang; Chong-Huai Yan (Science of The Total Environment, 2023)

A case of A133V genetic Creutzfeldt–Jakob disease presenting with bilateral thalamic lesions and atypical clinical features - Shi-Lin Yang; Shu-Fen Chen; Chong-Bo Zhao; Xiang Han (Acta Neurologica Belgica, 2023)

Study Method of Pile near Cohesionless Slope under Reversed Lateral Load Considering Sand Strength State and Lateral Deflection of Pile - Chong Jiang; Jing Liu; Mingke Lin (Journal of Marine Science and Engineering, 2023)
A p-y curve method of pile near cohesionless soil slope under reversed lateral load is proposed. This method takes into account the failure mode of soil around the pile under reversed lateral load and the interaction mode between pile and soil, and derives the ultimate soil resistance of the pile. Considering the change of the original stress state of soil due to the lateral deflection of the pile foundation, the influence of the relative density, the initial mean effective stress and the lateral deflection of pile foundation on the internal friction angle of the sand is evaluated to further accurately calculate the soil resistance value at each depth. The prediction results of this method are well verified by comparing with the FE results and centrifuge test results. Finally, the influence of the process of lateral deflection of pile on the strength state of soil around the pile and the bearing capacity of pile is studied.

Functionalized hierarchically porous carbon doped boron nitride for multipurpose and efficient treatment of radioactive sewage - Peng Zhang; Yawen Chen; Yizhi Chen; Qiqi Guo; Yusen Liu; Yu Yang; Qi Cao; Hanbao Chong; Mingzhang Lin (Science of The Total Environment, 2023)

Levels, distribution, sources and children health risk of PAHs in residential dust: A multi-city study in China - Xinqi Wang; Xiaoli Wang; Jing Qi; Shuhan Gong; Chong Wang; Li Li; Lin Fan; Hang Liu; Yun Cao; Mengmeng Liu; Xu Han; Liqin Su; et al. (Science of The Total Environment, 2023)

Layered porous carbon material derived from food residues and its application for elemental mercury adsorption in flue gas - Ao Wang; Wei Chen; Shengyan Liu; Wensheng Lin; Chong Tian (Fuel, 2023)

Experimental and kinetic model evaluation of HONO production from surface nitrate photolysis - Youfeng Wang; Jianshu Wang; Yaru Wang; Yingjie Zhang; Robert Woodward-Massey; Chong Zhang; Yu Kuang; Jiali Zhu; Jing Shang; Xin Li; Limin Zeng; Weili Lin; et al. (Atmospheric Environment, 2023)

Cross-species binding spectrum of ACE2 to SARS-CoV-2 RBD - Xihao Liao; Changge Guan; Chenghua Wang; Xinjie Chen; Xiaomei Lin; Lianghua Lu; Lu Li; Ting Wang; Nan Su; Bian Wu; Xinquan Wang; Chong Zhang; et al. (Science China Life Sciences, 2023)

Study on Dynamic Response of Soil Layer at the Bottom of Subway Shield Tunnel Under Seismic Action - Lexin Xu; Jiaqi Guo; Chong Xu; Ruimin Chen; Jinhai Lin (Geotechnical and Geological Engineering, 2023)

Construction and validation of a bladder cancer risk model based on autophagy-related genes - Chong Shen; Yan Yan; Shaobo Yang; Zejin Wang; Zhouliang Wu; Zhi Li; Zhe Zhang; Yuda Lin; Peng Li; Hailong Hu (Functional & Integrative Genomics, 2023)

Screening and characterization of sex-specific markers by NGS sequencing in Spinibarbus hollandi with implication of XY sex determination system - Chong Han; Wenwei Huang; Suhan Peng; Jiangwei Zhou; Huawei Zhan; Lin Gui; Wenjun Li; Qiang Li (Aquaculture, 2023)

Dosing with pyrite significantly increases anammox performance: Its role in the electron transfer enhancement and the functions of the Fe-N-S cycle - Fan Feng; Zhigong Liu; Xi Tang; Xing Wu; Caiyan Qu; Seow Wah How; Di Wu; Ruiyang Xiao; Chong-Jian Tang; Zhang Lin; Liyuan Chai; Guang-Hao Chen (Water Research, 2023)

Embryo developmental toxicity in marine medaka (Oryzias melastigma) due to parental and embryonic 17α-ethinylestradiol exposure - Xian Qin; Huiju Lin; Yaru Cao; Rudolf Shiu Sun Wu; Keng Po Lai; Richard Yuen Chong Kong (Science of The Total Environment, 2023)

Between the devil and the deep blue sea: Trends, drivers, and impacts of coastal reclamation in Malaysia and way forward - Su Yin Chee; Mou Leong Tan; Yi Lin Tew; Yee Kwang Sim; Jean Chai Yee; Amanda Kar Mun Chong (Science of The Total Environment, 2023)

Biotransformation of sulfamethoxazole (SMX) by aerobic granular sludge: Removal performance, degradation mechanism and microbial response - Bing Zhang; Yuankai He; Wenxin Shi; Lanjin Liu; Lin Li; Chong Liu; Piet N.L. Lens (Science of The Total Environment, 2023)

Kinetic insights into deoxygenation of vegetable oils to produce second-generation biodiesel - Dong Lin; Zhiwei Mao; Xiang Feng; Xin Zhou; Hao Yan; Huihong Zhu; Yibin Liu; Xiaobo Chen; Yongxiao Tuo; Chong Peng; De Chen; Chaohe Yang (Fuel, 2023)

Soil pH restricts the ability of biochar to passivate cadmium: A meta-analysis - Beilei Wei; Yunchang Peng; Paramsothy Jeyakumar; Longxin Lin; Dongliang Zhang; Meiyan Yang; Jinning Zhu; Carol Sze Ki Lin; Hailong Wang; Ziting Wang; Chong Li (Environmental Research, 2023)

Impact of miR-200b and miR-495 variants on the risk of large-artery atherosclerosis stroke - Shanmei Qin; Chong Shen; Wuzhuang Tang; Mengmeng Wang; Ying Lin; Zhaojun Wang; Yunzi Li; Zhizhong Zhang; Xinfeng Liu (Metabolic Brain Disease, 2023)

Effect of the proximity of slope and pile shape on lateral capacity of piles in clay slopes - Chong Jiang; Lin Liu; Jia-li He; Han-song Xie (European Journal of Environmental and Civil Engineering, 2023)

Effects of hyperosmotic stress on the intestinal microbiota, transcriptome, and immune function of mandarin fish (Siniperca chuatsi) - Haofeng Ouyang; Niuniu Deng; Jiachang Xu; Jingjun Huang; Chong Han; Dingrui Liu; Shiyan Liu; Baohua Yan; Linqiang Han; Shuisheng Li; Guifeng Li; Jin Zhang; et al. (Aquaculture, 2023)

Screening and characterization of X chromosome-specific markers in mandarin fish (Siniperca chuatsi) - Shiyan Liu; Chong Han; Jingjun Huang; Qiaoying Zhu; Dingrui Liu; Linqiang Han; Shuisheng Li; Guifeng Li; Haoran Lin; Yong Zhang (Aquaculture, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Chromatin modifiers: A new class of pollutants with potential epigenetic effects revealed by in vitro assays and transcriptomic analyses - Chi Tim Leung; Yi Yang; Ting Fung Chan; Xiao Lin; Alice Sze Tsai Wong; Wing Yee Lui; Karen Wing Yee Yuen; Richard Yuen Chong Kong; Keng Po Lai; Rudolf Shiu Sun Wu (Toxicology, 2023)

Petrogenesis of high heat production granite in eastern Hebei Province, China: Constraints from geochronology, geochemistry and Sr-Nd-Hf-O isotopes - Tao Zhang; De-Hui Zhang; Xiang-Chong Liu; Hua-Ning Qiu; Ji-Lin Zhang; Yan-Bing Liu (Lithos, 2023)

Contrast the distribution, transformation, and degradation of dissolved and particulate organic matter in the South Yellow Sea, the East China Sea, and its adjacent Kuroshio Current - Chong-Xiao Ji; Gui-Peng Yang; Yan Chen; Zhen He; Yan Li; Lin Zhang (Marine Chemistry, 2023)

The association of long-term ambient fine particulate matter exposure with blood pressure among Chinese adults - Zhennan Lin; Shufeng Chen; Fangchao Liu; Jianxin Li; Jie Cao; Keyong Huang; Fengchao Liang; Jichun Chen; Hongfan Li; Jianfeng Huang; Dongsheng Hu; Chong Shen; et al. (Environmental Pollution, 2023)

Corrigendum to “Novel diketopyrrolopyrrole NIR-II fluorophores and DDR inhibitors for in vivo Chemo-photodynamic therapy of Osteosarcoma” [Chem. Eng. J. 446 (2022) 136929] - Xiaoding Cheng; Chong Zhang; Kun Shen; Huifan Liu; Caihong Bai; Qihang Ding; Mengting Guan; Junzhu Wu; Zhiquan Tian; Deliang Chen; Lin Cai; Xuechuan Hong; et al. (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Temporal variations and trends prediction of water quality during 2010–2019 in the middle Yangtze River, China - Lin Chong; Jiwen Zhong; Zhilin Sun; Chunhong Hu (Environmental Science and Pollution Research, 2022)

7-Hydroxy questin, a new anthraquinone from a wetland fungus Aspergillus flavipes PJ03-11 - Chong Yu; Shuang Lin; Xiaorui Ma; Jie Zhang; Caixia Wu; Ben Ma; Haifeng Wang; Yuehu Pei (Natural Product Research, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Elevation of microRNA-365 impedes malignant behaviors of gastric cancer cells by inhibiting PAX6 - Dan Hong; Aimin Zang; Zhiyu Wang; Lin Yang; Guanying Ren; Chong Zhang; Liwei Zhang; Wei Hou; Yaning Wei (Functional & Integrative Genomics, 2022)

Temporal and spatial variation in water quality in the Yangtze Estuary from 2012 to 2018 - Lin Chong; Bao Li; Zhilin Sun; Chunhong Hu; Xin Meng; Jian Gao (Environmental Science and Pollution Research, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

IL-38, a potential therapeutic agent for lupus, inhibits lupus progression - Wang-Dong Xu; Lin-Chong Su; Lu Fu; You-Yu Lan; Xiao-Yan Liu; Qi Huang; Qian Wu; Jie Zhou; An-Fang Huang (Inflammation Research, 2022)

The characteristics of alkaline phosphatase activity and phoD gene community in heavy-metal contaminated soil remediated by biochar and compost - Haiwei Lu; Chong Xu; Jiachao Zhang; Chunyan Du; Genyi Wu; Lin Luo (Bulletin of Environmental Contamination and Toxicology, 2022)

Dynamics of antibiotic resistance genes and microbial community in shortcut nitrification–denitrification process under antibiotic stresses - Chong Yang; Lin Wang; Huan Wang; Hongyan Zhang; Fan Wang; Houzhen Zhou; Zhouliang Tan; Yangwu Chen (Environmental Science and Pollution Research, 2022)

Spatiotemporal characteristics and influencing factors of urban resilience efficiency in the Yangtze River Economic Belt, China - Yingzi Lin; Chong Peng; Jianfeng Shu; Wei Zhai; Jianquan Cheng (Environmental Science and Pollution Research, 2022)

Application of controlled-source audio-frequency magnetotellurics (CSAMT) for goaf detection: a case study in the Fangzi coal mine China - Kai Zhang; Niantian Lin; Xikun Nie; Chong Zhang; Xiaodong Wang; Gaopeng Tian; Jiuqiang Yang (Arabian Journal of Geosciences, 2022)

Legacy effects of a multi-year extreme drought on belowground bud banks in rhizomatous vs bunchgrass-dominated grasslands - Jianqiang Qian; Ziyue Guo; Taofeek O. Muraina; Niwu Te; Robert J. Griffin-Nolan; Lin Song; Chong Xu; Qiang Yu; Zhiming Zhang; Wentao Luo (Oecologia, 2022)

Enhanced effect of biochar on leaching vanadium and copper from stone coal tailings by Thiobacillus ferrooxidans - Yingbo Dong; Shijia Chong; Hai Lin (Environmental Science and Pollution Research, 2022)

Quantitative characterization of cracking process in oil shale using micro-CT imaging - Chong Lin; Jianming He; Yadong Liu; Jincheng Mao; Xiao Li; Xiaojiang Yang; Jinzhou Zhao (Arabian Journal of Geosciences, 2022)

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Isolation and structural elucidation of a low-molecular-weight polysaccharide from the roots of Panax ginseng C. A. Meyer - Bin Zhao; Xin-Ying Wang; Wen Luo; Yue Lin; Chong-Ning Lv; Jin-Cai Lu (Natural Product Research, 2022)

Nitrogen absorption by alpine forage species based on 15N tracer technique in a hydroponic culture - Yan-fang Liu; Wen-ying Wang; Xiao-lin Ma; Pan Liu; Hua-kun Zhou; Zhe Chen; Chong Yang; Jin-hong Guan (Journal of Mountain Science, 2021)

Reservoir Characterization Using Multi-component Seismic Data in a Novel Hybrid Model Based on Clustering and Deep Neural Network - Jiuqiang Yang; Niantian Lin; Kai Zhang; Chong Zhang; Chao Fu; Gaopeng Tian; Cuiyu Song (Natural Resources Research, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Baseline soundscapes of deep‐sea habitats reveal heterogeneity among ecosystems and sensitivity to anthropogenic impacts - Chong Chen; Tzu‐Hao Lin; Hiromi Kayama Watanabe; Tomonari Akamatsu; Shinsuke Kawagucci (Limnology and Oceanography, 2021)
Underwater soundscapes, though invisible, are crucial in shaping the biodiversity of marine ecosystems by acting as habitat‐specific settlement cues for larvae. The deep sea has received little attention in soundscape research, but it is being targeted for mineral extraction to feed the ever‐growing needs of our society. Anthropogenic impacts on soundscapes influence the resilience of key shallow‐water habitats, and the same likely applies to the deep. Japan is a forerunner in deep‐sea mining, but virtually no deep soundscape baselines exist for Japanese waters. Here, we report baseline soundscapes from four deep‐sea locations in Japan, including the Suiyo Seamount hydrothermal vent, the abyssal plain around the Minamitorishima Island home to manganese nodule fields and muds rich in rare‐earth elements, twilight depths off Sanriku, as well as a typical bathyal system in Suruga Bay. Long‐duration audio recordings were visualized and factorized by an unsupervised machine learning model, revealing differing characteristics among the habitats. Two locations near the coast are highly influenced by shipping noise. The Suiyo vent is characterized by low‐frequency sounds from venting, and the abyssal Minamitorishima is quiet with a flat spectral shape. Noise from observation platforms is likely sufficient to alter soundscape characteristics, especially in offshore locations, suggesting offshore mining‐targeted areas are susceptible to impacts from anthropogenic noise. We argue that the monitoring of soundscapes is an indispensable component for assessing potential mining impacts on deep‐sea ecosystems. Our results establish reference points for future soundscape monitoring and assessment in Japanese waters as well as similar ecosystems globally.

Spatiotemporal analysis of temperature data trends in Peninsular Malaysia - Hun Vui Woo; Jing Lin Ng; Yuk Feng Huang; Celine Chong; Jin Chai Lee (Arabian Journal of Geosciences, 2021)

Identification of potential sex-related genes in Siniperca chuatsi - Qiaoying Zhu; Chong Han; Cheng Peng; Xingni Zhou; Chongwei Wang; Linqiang Han; Shuisheng Li; Guifeng Li; Haoran Lin; Yong Zhang (Journal of Oceanology and Limnology, 2021)

Comparing the cost, glycaemic control and medication adherence of utilizing patients’ own medicines (POMs) versus usual dispensing among diabetic patients in an outpatient setting - Phei Ching Lim; Yin Ying Chung; Shien Joo Tan; Te Ying Wong; Durga Devi Permalu; Thean Kheng Cheah; Shueh Lin Lim; Chong Yew Lee (DARU Journal of Pharmaceutical Sciences, 2021)

Proteomic Response of the Brain to Hypoxic Stress in Marine Medaka Fish (Oryzias melastigma) - Keng Po Lai; Nathan Tam; Simon Yuan Wang; William Ka Fai Tse; Xiao Lin; Ting Fung Chan; Yin Tong; Jianwen Zhang; Doris Wai Ting Au; Rudolf Shiu Sun Wu; Richard Yuen Chong Kong (Frontiers in Marine Science, 2021)
Hypoxia is a serious issue that affects the marine environment, with a growing number of hypoxic “dead zones” occurring each year. Reports have indicated that hypoxia is detrimental to the reproductive function and sexual development of fish via the disruption of endocrine signaling in organs involved in the hypothalamus–pituitary–gonad axis, including the brain. While we previously reported that hypoxia induces transcriptome-wide alterations in the brain of marine medaka ( Oryzias melastigma ), whether these effects were reflected at the protein level remains unclear. Therefore, the present study used high-throughput proteomic sequencing along with bioinformatics analysis to assess the short-term and multi-generational effects of hypoxia on the brain proteome of O. melastigma . We identified 36,567 peptides and 7,599 proteins (1% false discovery rate in brain samples), with functions involved in cellular and metabolic processes such as signaling and reproductive processes as well as energy production and conversion. Furthermore, we determined that hypoxia resulted in the significant differential expressions of 33 upregulated and 69 downregulated proteins in the short-term exposure group and 24 upregulated and 52 downregulated proteins in the multi-generational exposure group. Pathway enrichment analysis of the deregulated proteins indicated that hypoxia could impair brain function by altering arachidonic acid metabolism, tight junctions, and adrenergic signaling under short-term hypoxic exposure and by altering p53 and PI3K–Akt signaling under multi-generational hypoxic exposure, which may lead to the onset of neurodegenerative disorders including Alzheimer’s disease and amyotrophic lateral sclerosis. Ingenuity pathway analysis of the deregulated proteins showed that hypoxia affected common signaling pathways in the brain (e.g., integrin, paxillin, and epithelial adherens junction signaling) under both short-term and multi-generational exposures. Hypoxia also deregulated pathways specific to short-term exposure (including integrin-linked kinase, calcium, and integrin signaling) and multi-generational exposure (including sphingosine-1-phosphate signaling, endocannabinoid neuronal synapse pathway, and endoplasmic reticulum stress pathway). Overall, our results provide additional insights into the mechanisms of hypoxia disrupting neuronal function at the protein level in marine medaka.

QTL mapping of the genetic basis of stem diameter in soybean - Chong-Yuan Sun; Yu-Ming Yang; Lin Jia; Xiao-Qian Liu; Huan-Qing Xu; Hai-Yan Lv; Zhong-Wen Huang; Dan Zhang (Planta, 2021)

Analytical Stress Solutions for a Deep Buried Circular Tunnel Under an Unsteady Temperature Field - Qian-xiang Cheng; Ai-zhong Lu; Chong-lin Yin (Rock Mechanics and Rock Engineering, 2021)

Porous Cd0.5Zn0.5S nanocages derived from ZIF-8: boosted photocatalytic performances under LED-visible light - Lin Wu; Huifen Fu; Qi Wei; Qian Zhao; Peng Wang; Chong-Chen Wang (Environmental Science and Pollution Research, 2021)

Influence of the Micro-deformation Characteristics of Binary Media on the Shear Behavior of Structural Plane - Hang Lin; Lu Han; Yixian Wang; Rihong Cao; Yanlin Zhao; Chong Jiang (Geotechnical and Geological Engineering, 2021)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Post discharge positive re-tests in COVID-19: common but clinically non-significant - Muhammad Syafiq Abdullah; Pui Lin Chong; Rosmonaliza Asli; Riamiza Natalie Momin; Babu Ivan Mani; Dhiya Metussin; Vui Heng Chong (Infectious Diseases, 2020)

The undrained vertical and horizontal bearing capacity of internal skirted foundation in clay - Chong Jiang; Liu Lin; Chen Li; Tian-Bin Li; Jiali He (European Journal of Environmental and Civil Engineering, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Correction to: Whole Exome Sequencing Identifies Two Novel Mutations in the Reticulon 4–Interacting Protein 1 Gene in a Chinese Family with Autosomal Recessive Optic Neuropathies - Xiao-Huan Zou; Xin-Xin Guo; Hui-Zhen Su; Chong Wang; En-Lin Dong; Ning Wang; Wan-Jin Chen; Qi-Jie Zhang (Journal of Molecular Neuroscience, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Role of coaggregation in the pathogenicity and prolonged colonisation of Vibrio cholerae - Yien Shin Toh; Soo Ling Yeoh; Ivan Kok Seng Yap; Cindy Shuan Ju Teh; Thin Thin Win; Kwai Lin Thong; Chun Wie Chong (Medical Microbiology and Immunology, 2019)

Propagation characteristics and aperture evolution of hydraulic fractures in heterogeneous granite cores - Chong Lin; Jincheng Mao; Jianming He; Xiao Li; Jinzhou Zhao (Arabian Journal of Geosciences, 2019)

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Wang Ma; Lin Song; Kenny Helsen; Yingchao Lin; Jiangping Cai; Qiang Yu; Zhengwen Wang; Melinda D. Smith; et al. (Plant and Soil, 2019)

Whole Exome Sequencing Identifies Two Novel Mutations in the Reticulon 4–Interacting Protein 1 Gene in a Chinese Family with Autosomal Recessive Optic Neuropathies - Xiao-Huan Zou; Xin-Xin Guo; Hui-Zhen Su; Chong Wang; En-Lin Dong; Ning Wang; Wan-Jin Chen; Qi-Jie Zhang (Journal of Molecular Neuroscience, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Agricultural Development and Implication for Wetlands Sustainability: A Case from Baoqing County, Northeast China - Chong Fang; Zhidan Wen; Lin Li; Jia Du; Ge Liu; Xiaodi Wang; Kaishan Song (Chinese Geographical Science, 2019)

Magnetic mineral diagenesis in sediments of saline lake Lop Nur - Wen Li; Gui-jin Mu; Yong-chong Lin; Hao-ze Song (Journal of Mountain Science, 2019)

Experimental and numerical analyses on working performance of a high arch dam with deep-seated joints: Yebatan arch dam, China - Wen Zhang; Yuan Chen; Bao-quan Yang; Lin Zhang; Chong Zhang; Xiao-qiang Liu (Arabian Journal of Geosciences, 2019)

Effects of topographic factors and aboveground vegetation carbon stocks on soil organic carbon in Moso bamboo forests - Huiyun Fang; Biyong Ji; Xu Deng; Jiayang Ying; Guomo Zhou; Yongjun Shi; Lin Xu; Jixing Tao; Yufeng Zhou; Chong Li; Hao Zheng (Plant and Soil, 2018)

Insights into the role of extracellular polymeric substances in Zn2+ adsorption in different biological sludge systems - Yu-Xia Song; Cheng-Hai Lu; Peng Liu; Xi-Lin Chai; Xi Chen; Xiao-Bo Min; Chong-Jian Tang; Li-Yuan Chai (Environmental Science and Pollution Research, 2018)

Pseudomonas pharmafabricae sp. nov., Isolated From Pharmaceutical Wastewater - Xiao-Yun Yu; Jing-Yu Zhai; Chen Wu; Chong-Ya Zhang; Jie-Ying Shi; Lin-Xian Ding; Min Wu (Current Microbiology, 2018)

Characterization of complete mitochondrial genomes of Mastacembelus erythrotaenia and Mastacembelus armatus (Synbranchiformes: Mastacembelidae) and phylogenetic studies of Mastacembelidae - Chong Han; Qiang Li; Jianfeng Lin; Zhipeng Zhang; Jianrong Huang (Conservation Genetics Resources, 2018)

An Experimental Study on Porosity and Permeability Stress-Sensitive Behavior of Sandstone Under Hydrostatic Compression: Characteristics, Mechanisms and Controlling Factors - Chengyuan Xu; Chong Lin; Yili Kang; Lijun You (Rock Mechanics and Rock Engineering, 2018)

Long-term groundwater storage changes and land subsidence development in the North China Plain (1971–2015) - Huili Gong; Yun Pan; Longqun Zheng; Xiaojuan Li; Lin Zhu; Chong Zhang; Zhiyong Huang; Zhiping Li; Haigang Wang; Chaofan Zhou (Hydrogeology Journal, 2018)

Sugars as supplemental cryoprotectants for marine organisms - Sujune Tsai; Gabriella Chong; Pei‐Jie Meng; Chiahsin Lin (Reviews in Aquaculture, 2018)
Cryopreservation has been extensively used in various mega‐industries and has recently been applied in genetic banking for conservation purposes. Compared with conventional cell preservation methods, cryopreservation can maintain the viability of cryopreserved cells for an indefinite time at a relatively lower cost and lesser manpower, with lower probabilities of contamination and genetic changes. This study presents the crucial role of sugar, a cryoprotectant supplement in cryopreservation. Sugar molecules typically interact with the lipid bilayer during the freezing phase to maintain plasma membrane integrity when cells undergo dehydration. When combined with other permeable cryoprotectants such as glucose with methanol and trehalose with dimethyl sulphoxide, sugar prolongs and enhances cellular post‐thaw viability. Moreover, terrestrial and marine organisms have benefited from the inclusion of sugar in the cryopreservation protocol. For wide range of cells such as the sperm, oocytes, embryos and larvae of marine vertebrates and invertebrates, as well as marine algae, cryopreservation with sugar produced positive results compared with cryopreservation without sugar. Not all sugar is beneficial, and the type and concentration of sugar should be applied according to the species. Moreover, the freezing method may also affect the function of sugar. Nevertheless, understanding the role of sugar in cryobiology and conducting a preliminary trial of sugar for cryopreserving cells would benefit future research on cryopreservation.

Water quality variation during a strong El Niño event in 2016: a case study in Kampar River, Malaysia - Casey Keat-Chuan Ng; Choo-Hou Goh; Jia-Chun Lin; Minn-Syenn Tan; Willie Bong; Chea-Soon Yong; Jun-Yao Chong; Peter Aun-Chuan Ooi; Wey-Lim Wong; Gideon Khoo (Environmental Monitoring and Assessment, 2018)

c.835-5T>G Variant in SMN1 Gene Causes Transcript Exclusion of Exon 7 and Spinal Muscular Atrophy - Shuang Wu; Yun-Lu Li; Ning-Yi Cheng; Chong Wang; En-Lin Dong; Ying-Qian Lu; Jin-Jing Li; Xin-Xin Guo; Xiang Lin; Lu-Lu Lai; Zhi-Wei Liu; Ning Wang; et al. (Journal of Molecular Neuroscience, 2018)

Width Evolution of the Hydraulic Fractures in Different Reservoir Rocks - Chong Lin; Jianming He; Xiao Li (Rock Mechanics and Rock Engineering, 2018)

CpG-PEG Conjugates and their Immune Modulating Effects after Systemic Administration - Caixing Wu; Xiaofei Xiang; Yang Yue; Lin Li; Yesen Li; Chong Zhang; Yuhong Xu (Pharmaceutical Research, 2018)

Ca2+-CaMKKβ pathway is required for adiponectin-induced secretion in rat submandibular gland - Chong Ding; Zhi-Hao Du; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2018)

A new arbutin derivative from the leaves of Vaccinium dunalianum wight - Na Li; Wei-Lin Zeng; Xu-Lu Luo; Chong-Ren Yang; Ying-Jun Zhang; Yong Ding; Ping Zhao (Natural Product Research, 2018)

Analysis of gene expression and functional characterization of XPR1: a pathogenic gene for primary familial brain calcification - Xiang-Ping Yao; Miao Zhao; Chong Wang; Xin-Xin Guo; Hui-Zhen Su; En-Lin Dong; Hai-Ting Chen; Jing-Hui Lai; Yao-Bin Liu; Ning Wang; Wan-Jin Chen (Cell and Tissue Research, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Microbial food safety assessment of dried edible mushrooms - Ana Hazirah Ajis; Lin June Chong; Yee Shin Tan; Lay Ching Chai (Journal of Consumer Protection and Food Safety, 2017)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Iron supply prevents Cd uptake in Arabidopsis by inhibiting IRT1 expression and favoring competition between Fe and Cd uptake - Xiao Lin He; Shi Kan Fan; Jun Zhu; Mei Yan Guan; Xing Xing Liu; Yong Song Zhang; Chong Wei Jin (Plant and Soil, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

Comparative analysis of the transcriptional responses to low and high temperatures in three rice planthopper species - Hai‐Jian Huang; Jian Xue; Ji‐Chong Zhuo; Ruo‐Lin Cheng; Hai‐Jun Xu; Chuan‐Xi Zhang (Molecular Ecology, 2017)
The brown planthopper ( Nilaparvata lugens , BPH ), white‐backed planthopper ( Sogatella furcifera , WBPH ) and small brown planthopper ( Laodelphax striatellus , SBPH ) are important rice pests in Asia. These three species differ in thermal tolerance and exhibit quite different migration and overwintering strategies. To understand the underlying mechanisms, we sequenced and compared the transcriptome of the three species under different temperature treatments. We found that metabolism‐, exoskeleton‐ and chemosensory‐related genes were modulated. In high temperature (37 °C), heat shock protein ( HSP ) genes were the most co‐regulated; other genes related with fatty acid metabolism, amino acid metabolism and transportation were also differentially expressed. In low temperature (5 °C), the differences in gene expression of the genes for fatty acid synthesis, transport proteins and cytochrome P450 might explain why SBPH can overwinter in high latitudes, while BPH and WBPH cannot. In addition, other genes related with moulting, and membrane lipid composition might also play roles in resistance to low and high temperatures. Our study illustrates the common responses and different tolerance mechanisms of three rice planthoppers in coping with temperature change, and provides a potential strategy for pest management.

An Experimental Investigation into the Effects of the Anisotropy of Shale on Hydraulic Fracture Propagation - Chong Lin; Jianming He; Xiao Li; Xiaole Wan; Bo Zheng (Rock Mechanics and Rock Engineering, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Research on China export structure adjustment: an embodied carbon perspective - Pi-qin Gong; Bao-jun Tang; Yu-chong Xiao; Gao-jie Lin; Jian-yun Liu (Natural Hazards, 2016)

Piperine potentiates the effects of trans-resveratrol on stress-induced depressive-like behavior: involvement of monoaminergic system and cAMP-dependent pathway - Ying Xu; Chong Zhang; Feiyan Wu; Xiaoxiao Xu; Gang Wang; Mengmeng Lin; Yingcong Yu; Yiran An; Jianchun Pan (Metabolic Brain Disease, 2016)

Illicit drugs and their metabolites in 36 rivers that drain into the Bohai Sea and north Yellow Sea, north China - De-Gao Wang; Qiu-Da Zheng; Xiao-Ping Wang; Juan Du; Chong-Guo Tian; Zhuang Wang; Lin-Ke Ge (Environmental Science and Pollution Research, 2016)

Greenhouse gas emissions and comprehensive greenhouse effect potential of Megalobrama amblycephala culture pond ecosystems in a 3-month growing season - Lin Zhu; Xuan Che; Huang Liu; Xingguo Liu; Chong Liu; Xiaolong Chen; Xu Shi (Aquaculture International, 2016)

Estimation of winter wheat phenology under the influence of cumulative temperature and soil salinity in the Yellow River Delta, China, using MODIS time-series data - Lin Chu; Chong Huang; Qing-sheng Liu; Gao-huan Liu (International Journal of Remote Sensing, 2016)

Application of the non-seismic geophysical method in the deep geological structure study of Benxi-Huanren area - Chong Peng; Lin-Fu Xue; Zheng-Hong Liu; Hai-Yan Liu (Arabian Journal of Geosciences, 2016)

Monsoonal and lunar variability in microzooplankton abundance and community structure in the Terusan mangrove creek (Malaysia) - Yu Lin Yong; Li Lee Chew; Choon Weng Lee; Ving Ching Chong (Marine Biology Research, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Using hybrid transcription factors to study gene function in rice - Tao Zhao; Jun Liu; Hong-Yu Li; Jian-Zhong Lin; Ming-Di Bian; Chun-Yu Zhang; Yong-Xing Zhang; Yu-Chong Peng; Bin Liu; ChenTao Lin (Science China Life Sciences, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions - J Chen; D Chee; Y Wang; G Y Lim; S M Chong; Y N Lin; T Huangfu (Journal of Fish Diseases, 2015)
Cyprinid herpesvirus 3 (Cy HV ‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 Cy HV ‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 ( n = 11) and European 4 ( n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF 29 and ORF 30 (marker I) as well as ORF 133 and its upstream region (marker II ) revealed viruses of genotypes J (I ++ II + ), U/I (I −− II − ), an intermediate genotype (I ++ II − ) and a novel genotype, I ++ II +Δ , which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II , while maintaining the I ++ allele of marker I. The I ++ II +Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

Regression Analysis of Non-iatrogenic Factors That Determine Adherence to Radiation Therapy - Xiangzhao Bu; Xuemei Fan; Dawei Hao; Lin Guo; Chengjun Wu; Chong Zhou (Cell Biochemistry and Biophysics, 2015)

Mapping soil salinity using a similarity-based prediction approach: A case study in Huanghe River Delta, China - Lin Yang; Chong Huang; Gaohuan Liu; Jing Liu; A-Xing Zhu (Chinese Geographical Science, 2015)

Predicting Global Seafloor Topography Using Multi-Source Data - Min zhang Hu; Jian cheng Li; Hui Li; Chong Yang Shen; Tao yong Jin; Le lin Xing (Marine Geodesy, 2015)

Isolation of mitochondria with cubic membrane morphology reveals specific ionic requirements for the preservation of membrane structure - Ketpin Chong; Olivia Li Ling Tan; Zakaria A. Almsherqi; Qingsong Lin; Sepp D. Kohlwein; Yuru Deng (Protoplasma, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Antidepressant-like effects of ferulic acid: involvement of serotonergic and norepinergic systems - Jianliang Chen; Dan Lin; Chong Zhang; Gaowen Li; Nianping Zhang; Lina Ruan; Qizhi Yan; Jianxin Li; Xuefeng Yu; Xupei Xie; Cong Pang; Liang Cao; et al. (Metabolic Brain Disease, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

GSK3β Promotes the Differentiation of Oligodendrocyte Precursor Cells via β-Catenin-Mediated Transcriptional Regulation - Liang Zhou; Chong-Yu Shao; Si-min Xu; Jiao Ma; Ya-Jun Xie; Lin Zhou; Peng Teng; Yin Wang; Mengsheng Qiu; Ying Shen (Molecular Neurobiology, 2014)

Role of SIRT1 in Streptococcus pneumoniae-induced human β-defensin-2 and interleukin-8 expression in A549 cell - Li Lin; Shun-hang Wen; Shu-zhen Guo; Xiao-yan Su; Hu-jun Wu; Lei Chong; Hai-lin Zhang; Wei-xi Zhang; Chang-chong Li (Molecular and Cellular Biochemistry, 2014)

Degradation of polycyclic aromatic hydrocarbons in a coking wastewater treatment plant residual by an O3/ultraviolet fluidized bed reactor - Chong Lin; Wanhui Zhang; Mengyang Yuan; Chunhua Feng; Yuan Ren; Chaohai Wei (Environmental Science and Pollution Research, 2014)

The high-level accumulation of n-3 polyunsaturated fatty acids in transgenic pigs harboring the n-3 fatty acid desaturase gene from Caenorhabditis briggsae - Yanrong Zhou; Yanli Lin; Xiaojie Wu; Chong Feng; Chuan Long; Fuyin Xiong; Ning Wang; Dengke Pan; Hongxing Chen (Transgenic Research, 2014)

Mutation of mpk6 enhances cadmium tolerance in Arabidopsis plants by alleviating oxidative stress - Chong-Wei Jin; Qian-Qian Mao; Bing-Fang Luo; Xian-Yong Lin; Shao-Ting Du (Plant and Soil, 2013)

Nitrate nutrition enhances nickel accumulation and toxicity in Arabidopsis plants - Yan Hu; Nai Shan Wang; Xu Jun Hu; Xian Yong Lin; Ying Feng; Chong Wei Jin (Plant and Soil, 2013)

Identification and removal of polycyclic aromatic hydrocarbons in wastewater treatment processes from coke production plants - Wanhui Zhang; Chaohai Wei; Bo Yan; Chunhua Feng; Guobao Zhao; Chong Lin; Mengyang Yuan; Chaofei Wu; Yuan Ren; Yun Hu (Environmental Science and Pollution Research, 2013)

Inhibition of matrix metalloproteinase-9 expression by docosahexaenoic acid mediated by heme oxygenase 1 in 12-O-tetradecanoylphorbol-13-acetate-induced MCF-7 human breast cancer cells - Haw-Wen Chen; Che-Yi Chao; Li-Lin Lin; Chia-Yang Lu; Kai-Li Liu; Chong-Kuei Lii; Chien-Chun Li (Archives of Toxicology, 2013)

Relationship Between Myocardial Bridging and Coronary Arteriosclerosis - Jian Ling Sun; Wei Min Huang; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Protection by chrysin, apigenin, and luteolin against oxidative stress is mediated by the Nrf2-dependent up-regulation of heme oxygenase 1 and glutamate cysteine ligase in rat primary hepatocytes - Chin-Shiu Huang; Chong-Kuei Lii; Ai-Hsuan Lin; Yu-Wen Yeh; Hsien-Tsung Yao; Chien-Chun Li; Tsu-Shing Wang; Haw-Wen Chen (Archives of Toxicology, 2013)

Infusion of Endothelial Progenitor Cells Accelerates Hematopoietic and Immune Reconstitution, and Ameliorates the Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Chong Chen; Guoliang Song; Zhiling Yan; Shijuan Xu; Lu Jia; Shuang Ding; Jiang Cao; Wei Chen; Hai Cheng; Zhenyu Li; Wei Sang; et al. (Cell Biochemistry and Biophysics, 2012)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Expression of connective tissue growth factor and interleukin-11 in intratumoral tissue is associated with poor survival after curative resection of hepatocellular carcinoma - Zuo-Lin Xiang; Zhao-Chong Zeng; Jia Fan; Zhao-You Tang; Hai-Ying Zeng (Molecular Biology Reports, 2012)

Urotensin upregulates transforming growth factor-β1 expression of asthma airway through ERK-dependent pathway - Wei-xi Zhang; Ya-feng Liang; Xiao-ming Wang; Ying Nie; Lei Chong; Li Lin; Chun Chen; Chang-chong Li (Molecular and Cellular Biochemistry, 2012)

The expression of HIF-1α in primary hepatocellular carcinoma and its correlation with radiotherapy response and clinical outcome - Zuo-Lin Xiang; Zhao-Chong Zeng; Jia Fan; Zhao-You Tang; Jian He; Hai-Ying Zeng; Joe Y. Chang (Molecular Biology Reports, 2012)

Expression of cytokeratin 19 and matrix metalloproteinase 2 predicts lymph node metastasis in hepatocellular carcinoma - Zuo-Lin Xiang; Zhao-Chong Zeng; Zhao-You Tang; Jia Fan; Hui-Chuan Sun; Yun-Shan Tan (Molecular Biology Reports, 2011)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Automatic Removal of Eye-Movement and Blink Artifacts from EEG Signals - Jun Feng Gao; Yong Yang; Pan Lin; Pei Wang; Chong Xun Zheng (Brain Topography, 2010)

Application of Recombinant Fusion Proteins for Tissue Engineering - Masato Nagaoka; Hu-Lin Jiang; Takashi Hoshiba; Toshihiro Akaike; Chong-Su Cho (Annals of Biomedical Engineering, 2010)

Fabrication of a Novel Core-Shell Gene Delivery System Based on a Brush-Like Polycation of α, β–Poly (L-Aspartate-Graft-PEI) - Jia-Hui Yu; Ji-Shan Quan; Jung-Taek Kwon; Cheng-Xiong Xu; Bo Sun; Hu-Lin Jiang; Jae-Woon Nah; Eun-Mi Kim; Hwan-Jeong Jeong; Myung-Haing Cho; Chong-Su Cho (Pharmaceutical Research, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Chondrogenesis of human periosteum-derived progenitor cells in atelocollagen - Yong-Soo Choi; Sang-Min Lim; Hyun-Chong Shin; Chang-Woo Lee; Sang-Lin Kim; Dong-Il Kim (Biotechnology Letters, 2007)

Copper‐dependent iron transport in coastal and oceanic diatoms - Maria T. Maldonado; Andrew E. Allen; Joanne S. Chong; Kevin Lin; Dan Leus; Nataliya Karpenko; Shannon L. Harris (Limnology and Oceanography, 2006)
We investigated the presence of plasmalemma‐bound copper‐containing oxidases associated with the inducible iron (Fe) transport system in two diatoms of the genus Thalassiosira . Under Fe‐limiting conditions, Thalassiosira oceanica , an oceanic isolate, was able to enzymatically oxidize inorganic Fe(II) extracellularly. This oxidase activity was dependent on copper (Cu) availability and diminished by exposure to a multi‐Cu oxidase (MCO) inhibitor. The rates of Fe uptake from ferrioxamine B by Fe‐limited T. oceanica were also dependent on Cu availability in the growth media. The effects of Cu limitation on Fe(II) oxidation and Fe uptake from ferrioxamine B were partially reversed after a short exposure to a Cu addition, indicating that the putative oxidases contain Cu. Limited physiological experiments were also performed with the coastal diatom Thalassiosira pseudonana and provided some evidence for putative Cu‐containing oxidases in the high‐affinity Fe transport system of this isolate. To support these preliminary physiological data, we searched the newly available T. pseudonan a genome for a multi‐Cu‐containing oxidase gene and, using real‐time polymerase chain reaction (PCR), quantified its expression under various Fe and Cu levels. We identified a putative MCO gene with predicted transmembrane domains and found that transcription levels of this gene were significantly elevated in Fe‐limited cells relative to Fe‐replete cells. These data collectively suggest that putative MCOs are part of the inducible Fe transport system of Fe‐limited diatoms, which act to oxidize Fe(II) following reductive dissociation of Fe(III) from strong organic complexes.

Adaptive filtering of evoked potentials using higher-order adaptive signal enhancer with genetic-type variable step-size prefilter - B. -S. Lin; B. -S. Lin; F. -C. Chong; F. Lai (Medical & Biological Engineering & Computing, 2005)

Chemical characters and antioxidative properties of sulfated polysaccharides from Laminaria japonica - Chang-Hu Xue; Yu Fang; Hong Lin; Lei Chen; Zhao-Jie Li; Deng Deng; Chong-Xiao Lu (Journal of Applied Phycology, 2001)

Ground-based remote sensing of LWC in cloud and rainfall by a combined dual-wavelength radar-radiometer system - Lin Hai; Xin Miaoxin; Wei Chong; Hao Yaokui; Zou Shouxiang (Advances in Atmospheric Sciences, 1985)